A copper-based nano-enzyme and a preparation method and application thereof

CN121731487BActive Publication Date: 2026-10-20THE FIRST AFFILIATED HOSPITAL OF GUANGZHOU MEDICAL UNIV (GUANGZHOU RESPIRATORY CENT)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511639530.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-11
Publication Date
2026-10-20
Estimated Expiration
2045-11-11

AI Technical Summary

Technical Problem

尽管有报道指出Cu掺杂的ZIF-8可构建具有类酶活性的Cu-ZIF8纳米酶,但催化位点不足和活性位点的协同作用弱限制其催化效率且粒径过大容易在尿液中沉降并受到周期性尿液的冲刷会严重影响在膀胱内局部感染灶的抗菌疗效

Benefits of technology

(1)创新的使用钌配合物Ru(II)与金属有机框架Cu-ZIF8合成一种具有良好生物相容性、稳定性、高效的新型纳米酶Cu-ZIF8-Ru用于治疗多重耐药尿路感染。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121731487B_ABST
    Figure CN121731487B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of copper-based nanoenzymes, the copper-based nanoenzymes include copper-doped ZIF-8 metal organic framework and ruthenium complex.The preparation method of the copper-based nanoenzymes includes the following steps: the preparation of copper metal organic framework;The preparation of copper-based nanoenzymes.The copper-based nanoenzymes of the present application are good in biocompatibility, good in stability and have high efficient enzyme activity effect, can be infused by temperature-sensitive hydrogel and in situ gelation slow-release to improve its enhanced sterilization and inhibit biofilm curative effect, effectively remove drug-resistant bacteria in bladder, is the effective strategy of precision treatment multiple drug-resistant urinary tract infection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanozyme technology, and in particular to a copper-based nanozyme, its preparation method, and its application. Background Technology

[0002] Multidrug-resistant urinary tract infections (MDR-UTIs) are becoming one of the most challenging and common infections globally, primarily due to the inappropriate use of broad-spectrum antibiotics and the spread of drug-resistant genes. MDR-UTIs are often caused by residual bacteria and biofilms, with persistent and intermittent inflammation leading to poor treatment outcomes and a high recurrence rate even after symptom relief. Although intravenous carbapenems or novel β-lactam / enzyme inhibitors can suppress MDR-UTIs, their availability and high cost limit their widespread application. Furthermore, diagnostic delays and time lags in drug sensitivity testing can delay treatment, and relapses accelerate the spread of resistance, increasing hospitalization rates and treatment costs. Therefore, there is an urgent need to find an effective treatment strategy to address the clinical challenges of MDR-UTIs.

[0003] Copper-dependent cell death (cuproptosis), a novel cell death mechanism, has attracted widespread attention. It is characterized by programmed cell death triggered by copper homeostasis imbalance. 2+ Abnormal accumulation within cells selectively binds to lipid-acyled TCA cycle enzymes, inducing protein aggregation, iron-sulfur cluster damage, and inhibition of the respiratory electron transport chain, thereby disrupting energy metabolism, exacerbating cellular oxidative stress, and ultimately leading to cell death. The TCA cycle exists not only in the mitochondria of eukaryotes but also in the cytoplasm of many prokaryotes. It induces Cu in bacteria... 2+ Overload may induce programmed bacterial death similar to copper death, which holds promise as a viable strategy for eradicating multidrug-resistant bacteria. Although copper is a vital trace metal element in organisms, it exhibits significant toxicity to cells when its concentration exceeds the safety limits of homeostasis mechanisms. 2+ Controlled release at the site of infection during antimicrobial therapy is crucial for protecting healthy tissue cells at the infection site. Furthermore, multidrug-resistant bacteria generally possess highly efficient efflux systems and sophisticated oxidative stress buffering mechanisms; therefore, inducing copper-like cell death alone often fails to achieve ideal therapeutic effects when treating multidrug-resistant bacterial infections. This suggests the necessity of combining other antimicrobial therapies to synergistically enhance bactericidal efficacy through copper-like cell death.

[0004] Nanozymes, possessing activity similar to natural enzymes, are widely used in catalytic antibacterial therapy due to their stable performance and highly efficient catalytic activity. Nanozymes generate reactive oxygen species (·OH, ·OH) by mimicking catalytic activities similar to oxidase-like (OXD), peroxidase-like (OPD), and glutathione peroxidase-like (GSH-px). 1 O2, O2 -Nanozymes (NZYs) destroy bacterial cell walls and the bacterial respiratory electron transport chain by consuming GSH, causing oxidative stress damage and thus achieving bactericidal effects. This process does not rely on the target of traditional antibiotics and can bypass drug resistance mechanisms such as target mutation, efflux pumps, and enzymatic degradation. Moreover, nanozymes can recycle substrates to achieve low-dose, sustained bactericidal effects. Simultaneously, nanozymes easily form synergistic therapeutic effects with photodynamic therapy to achieve ROS amplification and better antibacterial efficacy, providing a new pathway for the treatment of multidrug-resistant infections. Although photodynamic antibacterial therapy has significant advantages in broad-spectrum antibacterial activity and low drug resistance through ROS generation, insufficient delivery selectivity and complex microenvironments such as biofilms and urine limit the bactericidal efficacy of ROS-mediated treatment.

[0005] Furthermore, ROS-generating nanozyme-catalyzed antibacterial therapy often suffers from unsatisfactory bactericidal effects in vitro and in vivo due to the single active site of the enzyme and the easy decay of enzyme-like activity. Moreover, ROS-mediated bactericidal pathways are susceptible to oxidative stress tolerance caused by bacterial upregulation of antioxidant and stress defense mechanisms, thus weakening efficacy. Copper-like death, which can precisely regulate bacterial death, offers new possibilities for multimodal combination therapy. Combining copper-like death with nanozyme-catalyzed antibacterial therapy and photodynamic therapy holds promise for overcoming the limitations of these ROS-mediated bactericidal strategies. Therefore, a multimodal strategy integrating photodynamic therapy, catalytic antibacterial therapy, and other therapies using copper-like death is beneficial for improving the efficacy of bactericidal action and biofilm disruption, and reducing the progression of drug resistance. In addition, the limitation of most nanozymes having only a single active site in the catalytic reaction prevents the simultaneous optimization of the adsorption / desorption balance of intermediates, thus affecting catalytic efficiency and limiting nanozyme performance. Increasing the number of metal sites on nanozymes and introducing asymmetric coordination to optimize the local electronic composition of different metal active sites is a promising strategy for improving enzyme catalytic activity. The formation of bimetallic nanozymes by bridging heteronuclear metal atoms represents a new type of asymmetric coordination, which promotes the interaction between adjacent atoms, regulates the adsorption / desorption of oxygen intermediates, and lowers the reaction energy barrier.

[0006] Metal-organic frameworks (MOFs) are ideal carriers for constructing nanozymes with multi-metal active sites due to their high designability. Introducing heteronuclear metal neighboring sites into the same framework can optimize local electron distribution and enhance catalytic performance. ZIF-8 has long been used as a carrier or precursor for nanozymes due to its excellent structural stability, biocompatibility, tunable chemical composition, and high loading rate. Its pH-responsive degradation characteristics are particularly suitable for the slightly acidic environment of the urinary tract. Furthermore, Cu-doped ZIF-8 can effectively address the issue of free Cu. 2+ The problem is that it is easily inactivated by protein aggregation in normal physiological environments. It is noteworthy that there are reports indicating that the ZnT1 transporter in eukaryotic cells can promote intracellular Cu... 2+ Accumulation mediates copper death, exogenous Zn 2+Then it can competitively inhibit Cu 2+ Intake. Since bacteria lack the ZnT1 transporter protein, this structural difference is utilized to allow Cu-doped ZIF-8 to release Zn in the slightly acidic environment of the urinary tract. 2+ Antagonistic Cu 2+ Inflow into healthy cells within the infection site can improve biosafety. Although Cu-doped ZIF-8 has been reported to construct Cu-ZIF8 nanozymes with enzyme-like activity, insufficient catalytic sites and weak synergistic effects of active sites limit their catalytic efficiency. Furthermore, excessively large particle sizes easily lead to sedimentation in urine and are subject to periodic urinary flushing, severely impacting the antibacterial efficacy at local infection sites in the bladder. Ruthenium complexes are readily excited into highly oxidizing excited states, possessing the potential to act as synergistic metal-ligand units to regulate the metal active sites of nanozymes. Therefore, utilizing ruthenium complexes to regulate the local electron distribution of different metal active sites in nanozymes can enhance their catalytic activity.

[0007] In summary, the preparation of an antibacterial nanozyme with good biocompatibility, stability, high efficiency, and clear mechanism of action, and its use in bladder instillation with a temperature-sensitive hydrogel followed by in-situ gelation and sustained release to enhance its bactericidal and biofilm-inhibiting effects and effectively eliminate drug-resistant bacteria in the bladder, is an effective strategy for the precise treatment of multidrug-resistant urinary tract infections. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a copper-based nanozyme comprising a copper (Cu)-doped zeolite imidazole salt framework-8 (ZIF-8) metal-organic framework and a ruthenium complex.

[0009] In one embodiment, the raw materials for preparing the copper-based nanozyme include ruthenium complex (Ru(phen)2dppz2), copper nitrate, zinc nitrate, and 2-methylimidazole.

[0010] A second aspect of the present invention also provides a method for preparing the above-mentioned copper-based nanozyme, comprising the following steps: Preparation of copper metal-organic framework: Under nitrogen protection, copper nitrate, zinc nitrate and 2-methylimidazole were dissolved in organic solvents, mixed and stirred, centrifuged and washed to obtain copper metal-organic framework (Cu-ZIF8). Preparation of copper-based nanozymes: Under nitrogen protection, ruthenium complex and copper metal-organic framework were mixed, stirred in the dark, centrifuged, and washed to obtain copper-based nanozymes (Cu-ZIF8-Ru).

[0011] In one embodiment, the mixing time is 0.5 to 2 hours.

[0012] In one embodiment, the stirring time in the dark is 10-15 hours.

[0013] In one embodiment, in the preparation of the copper metal-organic framework, the organic solvent is methanol, and the washing is performed with methanol; In the preparation of the copper-based nanozyme, the nitrogen protection is carried out under a thermal environment, and the washing is performed with methanol. The preparation method of the ruthenium complex includes the following steps: dissolving phenazine ligand (dppz) and cis-dichlorobis(1,10-phenanthroline)ruthenium(II) (cis-[Ru(phen)2Cl2]) in a mixed solvent of ethanol (EtOH) and water, refluxing under nitrogen, purifying, performing anion exchange, removing volatiles, and recrystallizing to obtain the ruthenium complex.

[0014] In one embodiment, in the preparation of the ruthenium complex, the phenazine ligand : cis-dichlorobis(1,10-phenanthroline)ruthenium(II) is in a mass ratio of 1 : (0.1~1), the anion exchange is performed using potassium hexafluorophosphate (KPF6), and the purification is performed using a silica gel chromatography column.

[0015] In one embodiment, the mixed solvent of ethanol and water has a volume ratio of ethanol:water of (1~3):1.

[0016] In one embodiment, the reflux time is 6 to 10 hours.

[0017] In one embodiment, the silica gel chromatography column contains acetonitrile (CH3CN) and toluene in a volume ratio of (1~2):(1~2).

[0018] In one embodiment, the recrystallization is recrystallization from a solution of acetonitrile and diethyl ether (Et2O).

[0019] In one embodiment, the method for preparing cis-dichlorobis(1,10-phenanthroline)ruthenium(II) includes the following steps: Mix phenanthroline, ruthenium trichloride trihydrate (RuCl3·3H2O), lithium chloride and dimethylformamide (DMF), stir overnight, reduce pressure, add acetone, filter, and wash to obtain cis-dichlorobis(1,10-phenanthroline)ruthenium(II); According to the mass ratio, the phenanthrene: ruthenium trichloride trihydrate: lithium chloride is 1: (0.1~1): (0.5~2).

[0020] In one embodiment, the overnight stirring temperature is 110~130°C.

[0021] In one embodiment, the addition of acetone followed by filtration and washing is performed using ice water and acetone.

[0022] A third aspect of the present invention also provides a thermosensitive hydrogel, wherein the thermosensitive hydrogel comprises the above-described copper-based nanozyme, or the copper-based nanozyme obtained by the above preparation method.

[0023] A fourth aspect of the present invention also provides a method for preparing the above-mentioned thermosensitive hydrogel, comprising the following steps: under nitrogen protection, degassing and stirring the initiator, adding D,L-lactide (LA) and glycolide (GA) and mixing, adding a catalyst to react, after the reaction is completed, pouring into water at 3~5°C, stirring overnight, heating in a water bath, adding copper-based nanozyme and mixing, and freeze-drying to obtain the thermosensitive hydrogel (Cu-ZIF8-Ru@Gel).

[0024] In one embodiment, the initiator is polyethylene glycol (PEG) and the catalyst is stannous isooctanoate (Sn(Oct)2). According to the mass ratio, the total mass of D,L-lactide and glycolide is (1~3):1 of polyethylene glycol. According to the molar ratio, the D,L-lactide : the glycolide is (6~8):1.

[0025] In one embodiment, the polyethylene glycol has a molecular weight of 1500.

[0026] In one embodiment, the stirring is performed at 140-160°C for 1-3 hours.

[0027] In one embodiment, the mixture of D,L-lactide and glycolide is kept under nitrogen atmosphere for 0.1 to 1 hour.

[0028] In one embodiment, the reaction temperature with added catalyst is 140~160°C, and the reaction time is 8~12h.

[0029] In one embodiment, the water bath heating temperature is 75~85°C.

[0030] In addition, the present invention also provides the application of the above-mentioned copper-based nanozyme or the copper-based nanozyme obtained by the above preparation method in the preparation of products for treating multidrug-resistant urinary tract infections.

[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) Innovatively using ruthenium complex Ru(II) and metal-organic framework Cu-ZIF8 to synthesize a novel nanozyme Cu-ZIF8-Ru with good biocompatibility, stability and high efficiency for the treatment of multidrug resistant urinary tract infections.

[0032] (2) For the first time, a novel nanozyme Cu-ZIF8-Ru with asymmetric Cu-N-Ru heteronuclear metal sites was synthesized by modifying the metal-organic framework Cu-ZIF8 with ruthenium complex Ru(II). By increasing the surface active sites and enhancing electron transfer efficiency, the efficiency of generating reactive oxygen species was improved, providing a new strategy for nanozyme treatment of multidrug-resistant bacteria.

[0033] (3) The design and synthesis method of this nanozyme is highly controllable and reproducible, which is conducive to large-scale production and clinical translation. Attached Figure Description

[0034] Figure 1 A schematic diagram illustrating the preparation process of Cu-ZIF8-Ru nanozyme and its principle for treating multidrug-resistant urinary tract infections. Figure 2 Characterization results of the composition and structure of Cu-ZIF8-Ru nanozymes; Figure 3 The results show the molecular assembly mechanism of Cu-ZIF8-Ru nanozymes; Figure 4 Results of multi-enzyme activity and catalytic ability of Cu-ZIF8-Ru nanozymes; Figure 5 The results show the mechanism by which Cu-ZIF8-Ru nanozymes enhance enzyme activity; Figure 6 The efficacy results of Cu-ZIF8-Ru nanozyme in in vitro treatment of multidrug-resistant bacteria; Figure 7 The mechanism by which Cu-ZIF8-Ru nanozymes kill multidrug-resistant bacteria; Figure 8 and Figure 9 Efficacy evaluation of Cu-ZIF8-Ru nanozyme thermosensitive hydrogel in vivo for the treatment of multidrug-resistant urinary tract infections. Detailed Implementation

[0035] In order to enhance the catalytic efficiency of nanozymes and achieve efficient antibacterial effects, and to develop new strategies for the treatment of multidrug-resistant urinary tract infections, the present invention aims to overcome the shortcomings of the prior art and provide an antibacterial copper-based nanozyme that has good biocompatibility, good stability, efficient enzyme activity, and a clear mechanism of action, which can be used to treat multidrug-resistant urinary tract infections.

[0036] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0038] Unless otherwise specified, all reagents, materials, and equipment used in this embodiment are commercially available; unless otherwise specified, all test methods are conventional test methods in this field.

[0039] Example I. This invention provides a method for preparing a copper-based nanozyme that can be used to treat urinary tract infections caused by multidrug-resistant bacteria, comprising the following steps: 0.6845 g of phenanthroline, 0.50 g of RuCl3·3H2O, and 0.80 g of lithium chloride were added to a 100 mL round-bottom flask with dimethylformamide (DMF, 20 mL) and stirred overnight at 120 °C. DMF was removed under reduced pressure, and the residue was treated with acetone (50 mL) and filtered to give a brownish-black solid. The solid was washed with ice water (10 mL) and acetone (50 mL) to give cis-[Ru(phen)2Cl2]. 0.653 g of cis-[Ru(phen)2Cl2] and 1.10 g of dppz were dissolved in EtOH / H2O (50 / 25 mL) and refluxed under N2 for 8 h to give an orange product. The crude product was purified by silica gel chromatography (CH3CN:toluene = 1:1, v / v) followed by anion exchange with KPF6 (1.0 g). After removing the volatiles, the remaining solid was recrystallized from CH3CN / Et2O to obtain Ru(phen)2dppz2.

[0040] Under nitrogen protection, appropriate amounts of copper nitrate, zinc nitrate, and 2-methylimidazole were dissolved in methanol, mixed and stirred at room temperature, and the mixture was centrifuged at high speed. The precipitate was then washed with methanol to obtain the Cu-ZIF8 metal-organic framework. The above metal-organic framework was then mixed with ruthenium complex under nitrogen protection in a light-protected thermal environment with low-speed stirring. After centrifugation, the precipitate was washed with methanol to obtain the Cu-ZIF8-Ru metal-organic framework nanozyme.

[0041] II. This invention also provides a method for preparing Cu-ZIF8-Ru nanozyme thermosensitive hydrogel, comprising the following steps: Under nitrogen protection, a PLGA-PEG-PLGA triblock copolymer was prepared by ring-opening polymerization of D,L-lactide (LA) and glycolide (GA) using polyethylene glycol (PEG) as the initiator and Sn(Oct)2 as the catalyst. The resulting solution was immediately poured into deionized water and stirred overnight under nitrogen protection. The product was heated in a water bath to remove unreacted monomers and water-soluble low-molecular-weight byproducts, yielding a PLGA-PEG-PLGA hydrogel. Cu-ZIF8-Ru and the PLGA-PEG-PLGA hydrogel were mixed at a volume ratio of 1:3 to obtain the product Cu-ZIF8-Ru-Gel. The sol-gel rheological properties of PLGA-PEG-PLGA and Cu-ZIF8-Ru-Gel, such as phase transition temperature, were determined using a Malvern rotational rheometer to evaluate the feasibility of bladder instillation of Cu-ZIF8-Ru nanozymes.

[0042] III. This invention also provides a method for preparing ICG-labeled Cu-ZIF8-Ru@Gel nanozyme hydrogels, comprising the following steps: Synthesis of ICG-labeled Cu-ZIF8-Ru and Cu-ZIF8-Ru@Gel: (1) Mix 500uL of 1mg / mL ICG with 500uL of 100μg / mL Cu-ZIF8-Ru and stir at low speed for 12h in the dark. After high-speed centrifugation, collect the precipitate and resuspend it to obtain ICG-labeled Cu-ZIF8-Ru; (2) Mix ICG-labeled Cu-ZIF8-Ru and PLGA-PEG-PLGA hydrogel at a volume ratio of 1:2 and stir at low speed overnight at room temperature to obtain ICG-labeled Cu-ZIF8-Ru@Gel nanozyme hydrogel.

[0043] IV. The following are the methods for evaluating the effects of the prepared Cu-ZIF8-Ru nanozymes and Cu-ZIF8-Ru@Gel nanozyme hydrogels in the embodiments of the present invention: 1. Characterization of Cu-ZIF8-Ru nanozymes The synthesized composite nanoparticles were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The particle size distribution of the composite nanoparticles was analyzed using a nanoparticle size analyzer. X-ray photoelectron spectroscopy (XPS) and elemental mapping analysis were used to detect changes in the elemental composition and valence state spectra of the composite nanoparticles. The stability of Cu-ZIF8-Ru nanozymes and the mechanism of enhanced acoustic dynamics were evaluated using mesoporous analysis, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), electron spin resonance (ESR), and Zeta potential. The enzyme activity level of Cu-ZIF8-Ru gold nanozymes was evaluated using different probes. Synchrotron radiation and DFT calculations were used to verify the molecular assembly mechanism and the mechanism of enhanced enzyme activity of Cu-ZIF8-Ru metal-organic framework nanozymes.

[0044] 2. Antibacterial efficacy and mechanism of Cu-ZIF8-Ru nanozyme (1) Biosafety evaluation: Under in vitro conditions, Escherichia coli, Bacillus mirabilis, human umbilical vein endothelial cells, and normal bladder epithelial cells were treated with different concentrations of Cu-ZIF8-Ru nanoparticles. The effects of Cu-ZIF8-Ru metal-organic framework on the proliferation of bacteria, human umbilical vein endothelial cells, and normal bladder epithelial cells were detected by agar plate counting and Alma blue reagent method, respectively, and cell lines with the most effective treatment time and good specificity were preliminarily screened. The safe concentration range of Cu-ZIF8-Ru-Gel nanoparticles was evaluated by co-incubating them with animal blood. Based on this, the preparation process of composite nanoparticles was optimized, and the safe range of copper content in composite nanoparticles was preliminarily determined.

[0045] (2) Study on the antibacterial effect of Cu-ZIF8-Ru nanozymes: The cell membrane damage effect of Cu-ZIF8-Ru nanoparticles on Escherichia coli and Bacillus mirabilis was observed using bioelectron microscopy. The effects of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru nanoparticles on the activity of Escherichia coli and Bacillus mirabilis were evaluated using a live-dead cell double staining kit and a plating method. The accumulation of copper ions in Escherichia coli by Cu-ZIF8-Ru nanoparticles was analyzed using mapping element analysis. The effects of reactive oxygen species (ROS) probes, DiSC3(5) probes, bacterial DNA kits, and ATP detection kits on the ROS level, membrane potential changes, DNA content, and ATP level of E. coli cells before and after laser irradiation were detected using ROS probes, DiSC3(5) probes, bacterial DNA kits, and ATP detection kits, preliminarily revealing the antibacterial mechanism of Cu-ZIF8-Ru metal-organic framework nanozymes.

[0046] (3) Antibacterial mechanism of Cu-ZIF8-Ru nanozyme: grouped into Control group, Cu 2+Groups three were identified: the Cu-ZIF8-Ru group and the Cu-ZIF8-Ru+Laser group. Escherichia coli in the logarithmic growth phase was collected and treated with the same concentration of Cu-ZIF8-Ru (Cu...). 2+ After quantitative incubation, the treated bacteria were collected for transcriptomics analysis to explore the potential mechanism of Cu-ZIF8-Ru nanoparticles in inhibiting bacterial activity and the crosstalk between signaling pathways, thereby conducting an in-depth analysis of the antibacterial mechanism of Cu-ZIF8-Ru metal-organic framework nanozymes.

[0047] 3. In vivo antibacterial efficacy of Cu-ZIF8-Ru nanozyme thermosensitive hydrogel A chronic urinary tract infection model was established using C57BL / 6 mice, and Cu-ZIF8-Ru-Gel was administered via bladder instillation. The in vivo antibacterial activity of Cu-ZIF8-Ru-Gel was evaluated using body weight and post-treatment bladder tissue homogenate plating as test indicators. After treatment, bladder, kidney, and blood samples were collected; complete blood counts and bacterial counts were performed in the bladder and kidneys. H&E staining, IL-6 staining, and CD68 staining were used at the bladder and kidney tissue levels to observe the antibacterial effect of Cu-ZIF8-Ru-Gel against bladder bacterial infection, comprehensively evaluating the in vivo antibacterial activity of this nanoparticle in the chronic urinary tract infection model.

[0048] The mechanism diagram of the present invention is as follows: Figure 1 As shown: Cu-ZIF8 and Ru(II) form Cu-N-Ru bridging coordination bonds to construct Cu-ZIF8-Ru nanozymes. Cu-ZIF8-Ru nanozymes induce oxidative stress by adhering to bacteria, generating large amounts of ROS, which damages the bacterial cell membrane and alters its permeability. The low pH environment of the bladder enables the acid degradation of Cu-ZIF8-Ru, releasing zinc ions (Zn). 2+ and copper ions Cu 2+ Achieving high levels of Cu in cells 2+ Enrichment triggers copper-based cell death in bacteria, further enhancing the therapeutic effect of killing bacteria. An injectable, thermosensitive acid-responsive hydrogel loaded with Cu-ZIF8-Ru nanozyme improves the stability and sustained-release capacity of the nanoparticles, increasing the adhesion probability of Cu-ZIF8-Ru to bacteria. Furthermore, the design and synthesis method of this nanomedicine is highly controllable and reproducible, facilitating large-scale production and clinical translation.

[0049] The present invention will be further described in detail below through specific embodiments.

[0050] Example 1 1. Preparation of Cu-ZIF8-Ru nanozymes Precise design and synthesis of Cu-ZIF8-Ru nanozymes: 0.6845 g of phenanthroline, 0.50 g of RuCl3·3H2O, and 0.80 g of lithium chloride were added to a 100 mL round-bottom flask along with dimethylformamide (DMF, 20 mL) and stirred overnight at 120 °C. DMF was removed under reduced pressure, and the residue was treated with acetone (50 mL) and filtered to obtain a brownish-black solid. The solid was washed with ice water (10 mL) and acetone (50 mL) to obtain cis-[Ru(phen)2Cl2]. 0.653 g of cis-[Ru(phen)2Cl2] and 1.10 g of dppz were dissolved in EtOH / H2O (50 / 25 mL) and refluxed under N2 for 8 h to obtain an orange product. The crude product was purified by silica gel chromatography (CH3CN:toluene = 1:1 by volume) and then anion exchanged with KPF6 (1.0 g). After removal of volatiles, the remaining solid was recrystallized from CH3CN / Et2O to give Ru(phen)2dppz2.

[0051] Under nitrogen protection, appropriate amounts of copper nitrate, zinc nitrate, and 660 mg of 2-methylimidazole were dissolved in 11.3 mL of methanol. The solutions were mixed and stirred at room temperature for 1 h. After high-speed centrifugation, the precipitate was washed with methanol to obtain the Cu-ZIF8 metal-organic framework. The above metal-organic framework and ruthenium complex were then stirred at low speed in a nitrogen-protected thermal environment in the dark for 12 h. After centrifugation, the precipitate was washed with methanol to obtain the Cu-ZIF8-Ru metal-organic framework nanozyme.

[0052] 2. Structural characterization and molecular assembly mechanism analysis of Cu-ZIF8-Ru nanozymes (1) Structural characterization of Cu-ZIF8-Ru nanozymes First, a Cu-ZIF8 ruthenium complex [Ru(phen)2bppz] was synthesized using Cu-doped ZIF-8. 2+ Ru(II) has advantages such as easy modification and high activity. Based on this, Cu-ZIF8 and Ru(II) were dissolved in DSMO and the mixture was stirred for at least 12 h in a light-protected environment to obtain the product Cu-ZIF8-Ru.

[0053] Results analysis: Transmission electron microscopy (TEM) Figure 2 A) The uniform polyhedral morphology of Cu-ZIF8-Ru is clearly visible. Compared to Cu-ZIF8, its contour surface is smoother, and no aggregates or large particles are observed, indicating that Cu-ZIF8-Ru is well dispersed. The zeta potential of Cu-ZIF8-Ru is significantly higher than that of Ru(II), and similar to that of Cu-ZIF8 and Cu-ZIF8-Ru. Figure 2(B) indicates that Cu-ZIF8-Ru exhibits good colloidal stability and dispersibility, consistent with TEM observations. A comparison of the morphology and particle size changes between Cu-ZIF8 and Cu-ZIF8-Ru ( Figure 2 (C) The results showed that the average particle size of Cu-ZIF8-Ru was approximately 209 nm, an increase of about 9 nm compared to Cu-ZIF8. Furthermore, the X-ray diffraction (XRD) pattern ( Figure 2 D) Confirms that the diffraction peaks of Cu-ZIF8-Ru are highly consistent with those of Cu-ZIF8, indicating that its framework structure is preserved. Correspondingly, the energy-dispersive X-ray mapping (EEDX) shows... Figure 2 E) clearly reveals that C, N, O, Zn, Cu and Ru are uniformly dispersed in the space of the polyhedron, which confirms that Ru(II) is uniformly distributed rather than a surface cluster, indicating that Ru(II) was successfully introduced into Cu-ZIF8 to successfully construct Cu-ZIF8-Ru.

[0054] The pore size distribution of Cu-ZIF8 and Cu-ZIF8-Ru was measured using the Brunauer-Emmett-Teller (BET) method. Figure 2 F-2G was used to further confirm the change in pore size of Cu-ZIF8-Ru nanoparticles after the introduction of Ru(II). The N2 adsorption / desorption isotherms of both Cu-ZIF8 and Cu-ZIF8-Ru exhibited typical type IV isotherms with a significant type H3 hysteresis loop, revealing that Cu-ZIF8-Ru is mainly composed of slit-type mesopores formed by particle packing, with a small number of micropores. It is noteworthy that, compared with Cu-ZIF8 (BET=1321.2m... 2 ·g -1 Compared to Cu-ZIF8-Ru (BET=1189.2m), 2 ·g -1 The adsorption volume and specific surface area of ​​Cu(II) decreased slightly, indicating that Ru(II) occupied some of the high specific surface area sites in Cu-ZIF8 (especially micropores / defect sites), but did not cause framework collapse or pore blockage. The large specific surface area can greatly expose a large number of active sites, enhancing the contact between Cu-ZIF8-Ru and the substrate. In addition, the pore size increased from Cu-ZIF8 (Pore diameter = 2.5 nm) to Cu-ZIF8-Ru (Pore diameter = 3.6 nm), indicating that Ru(II) did not agglomerate and block pores, but preferentially entered Cu-ZIF8 at the pore opening and partially occupied the micropores and changed the pore opening microstructure, while retaining or even slightly widening the mesoporous channels of Cu-ZIF8-Ru.

[0055] Further spectral analysis using a combination of UV-Vis and FTIR revealed that the introduction of Ru(II) altered the electronic valence state and coordination environment in the Cu-ZIF8-Ru structure. A comparison of the UV-Vis absorption spectra of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru showed that… Figure 2 The main absorption band of H)Ru(II) is approximately 445 nm, while the shoulder band is approximately 372 nm. The main absorption band of Cu-ZIF8-Ru redshifts to 455 nm and retains a shoulder band of 384 nm in the short-wavelength region, indicating the presence of Ru(II) in Cu-ZIF8-Ru. The redshift in the Cu-ZIF8-Ru spectrum confirms its electronic coupling characteristics, suggesting that the introduction of Ru(II) not only alters the energy level arrangement of Cu-ZIF8 but also triggers new charge transfer pathways, potentially leading to new metallic coordination environments.

[0056] To verify the possibility of electronic transitions reconstructing the coordination environment of Cu-ZIF8-Ru as revealed by UV-Vis spectroscopy, FTIR was used to further observe the vibrational changes of the metal-coordination bonds to confirm the alteration of the coordination environment. The FTIR absorption spectrum of Cu-ZIF8 is in the low wavenumber region, ~421.8 cm⁻¹. -1 The presence of a characteristic vibrational peak in metal-nitrogen (Zn / Cu-N) coordination bonds is a key indicator of framing in ZIF-type materials. Figure 2 I); and the characteristic vibrational peaks of the ring (such as ~995, ~760 cm⁻¹) -1 The presence of the imidazole ring in Cu-ZIF8 further confirms the integrity and ordered connection of the Cu-ZIF8 imidazole ring structure. Unlike Cu-ZIF8, the FTIR absorption spectrum of Cu-ZIF8-Ru shows that its C=N ratio is ~1500-1600 cm⁻¹. -1 ), CN (~1100-1300cm) -1 ) and Metal-N (<~500cm) -1 The vibrational peaks of Ru(II) showed an overall redshift and a decreasing vibrational frequency. The redshift of C=N and CN indicates a change in the electron density and local coordination field of the nitrogen ligand. Ru(II) induces electron traction in the nitrogen-containing ligand (2-methylimidazole) in Cu-ZIF8, leading to a decrease in resonance frequency, which is consistent with the UV-Vis spectral analysis results. It is speculated that this may be due to the disintegration of the Ru(II) structure caused by prolonged stirring of Ru(II) and Cu-ZIF8 in a polar solution, resulting in the generation of free Ru ions. These Ru ions then enter the pores of Cu-ZIF8 and interact with Cu-N. Combined with the UV-Vis spectroscopy revealing a new charge transfer pathway in Cu-ZIF8-Ru, and the FTIR spectroscopy confirming the presence of new metal coordination bond vibrations in Cu-ZIF8-Ru, it is speculated that the heavy metal element Ru in Ru(II) coordinates with Cu through the formation of coordination bonds to achieve a new charge transfer pathway.

[0057] The results of UV-Vis and FTIR revealed that the introduction of Ru(II) enhanced the coupling between electronic transitions and bond vibrations in Cu-ZIF8-Ru, but it was still impossible to distinguish the specific valence state and coordination electron effects. To understand the changes in valence state and coordination electron effects of the elements in the Cu-ZIF8-Ru surface layer, the XPS high-resolution spectra of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru were further analyzed. Compared with Cu-ZIF8 ( Figure 2 In Cu-ZIF8-Ru, the Cu2p atoms shift by 0.2 eV and 0.4 eV towards higher binding energies at Cu2p3 / 2 (933.1 eV) and Cu2p1 / 2 (953.1 eV), respectively. This indicates that the introduction of Ru leads to a decrease in the local electron cloud density of Cu atoms in Cu-ZIF8-Ru, an increase in valence state, and an enhanced ligand field. This can be attributed to the influence of electron traction from other metal atoms on Cu atoms in Cu-ZIF8-Ru. In the Ru3d XPS spectrum of Ru(II), the binding energies of Ru3d5 / 2 and Ru3d3 / 2 are 280.7 eV and 284.6 eV, respectively. Figure 2 In the Ru3d XPS spectrum of Cu-ZIF8-Ru, only the Ru3d3 / 2 binding energy appears with a value of 284.8 eV. This may be related to the fact that some Ru is located within the mesopores of Cu-ZIF8-Ru, and that Cu-ZIF8-Ru contains a large number of C atoms that shield the Ru3d3 / 2 signal. In the Ru3p XPS spectrum of Ru(II), the binding energies of Ru3p3 / 2 and Ru3p1 / 2 are 461.9 eV and 484.2 eV, respectively. Figure 2 The Ru3p XPS spectrum of Cu-ZIF8-Ru shows a Ru3p1 / 2 binding energy of 483.7 eV, indicating a 0.5 eV shift in Ru3p towards lower binding energies compared to Ru(II). This suggests an increased local electron cloud density in Ru atoms within Cu-ZIF8-Ru, with electrons more concentrated on the Ru atoms. Notably, the Ru3p XPS spectrum of ZIF8-Ru exhibits a new characteristic peak at a binding energy of 472.9 eV, which overlaps with the low binding energy envelope of Ru3p3 / 2 to form a shoulder with a binding energy of 476.0 eV. The Ru3p XPS spectrum of Ru(II) does not show a similar peak. Based on these results, it is inferred that the heavy metal element Ru in Ru(II) forms a Cu-N-Ru bridging coordination bond with the Cu-N3 saturated coordination bond. Furthermore, compared to Cu-ZIF8, the N1s of Cu-ZIF8-Ru shifts towards lower binding energies by 0.2 eV (MN, 398.6 eV) and 0.3 eV (CN, 399.1 eV), respectively. Figure 2The presence of Ru (M) indicates that the introduction of Ru leads to an increase in the local electron cloud density of the N atom in Cu-ZIF8-Ru, with N participating in the coordination of Ru and gaining electron feedback. The Cu2p of Cu-ZIF8-Ru shifts towards a higher binding energy direction, revealing an electron redistribution induced by Ru bridging through nitrogen atoms, confirming the formation of Cu-N-Ru coordination sites in Cu-ZIF8-Ru.

[0058] (2) Analysis of the molecular assembly mechanism of Cu-ZIF8-Ru nanozymes To further confirm the formation of Cu-N-Ru coordination sites in Cu-ZIF8-Ru, X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopy were used to reveal the coordination environment of Ru and Cu centers in Cu-ZIF8-Ru at the atomic level, with Ru, Cu foil and corresponding metal oxides used as control samples.

[0059] Results analysis: like Figure 3 As shown in Figure A, the near-edge absorption threshold of the Ru K-edge XANES spectrum of Cu-ZIF8-Ru is significantly higher than that of Ru foil (Ru0) but lower than that of RuO2 (Ru). 4+ The intensity of the white line is also between the two. This indicates that the average valence state of Ru in Cu-ZIF8-Ru is close to +2, ruling out the possibility of metallic Ru clusters or highly oxidized RuO2 as the main phase. This is further supported by observing the EXAFS oscillation curve of the Ru K-side in Cu-ZIF8-Ru. Figure 3 (B) The amplitude of Cu-ZIF8-Ru is significantly reduced and the period is slower compared to the two references, and it matches the fitted curve well. The low amplitude indicates that the first coordination shell of Ru atoms is poorly coordinated and has a high degree of local disorder, and the typical strong high-frequency oscillation characteristics of metallic Ru were not observed. This indicates that Ru in Cu-ZIF8-Ru exists as a dispersed coordination center dominated by Ru-N, rather than Ru-Ru metal neighbor or Ru-O oxide.

[0060] The Ru K-edge EXAFS Fourier transform spectrum of Cu-ZIF8-Ru shows ( Figure 3(c) A Ru-Ru coordination peak appears near 2.39 Å in the Ru foil, while a Ru-O-Ru path characteristic is observed in RuO2 at 1.53 Å. Notably, a moderate-intensity peak appears near 1.51 Å in Cu-ZIF8-Ru, which can be attributed to the first coordination shell peak of Ru-N; moreover, a secondary peak different from that of Ru foil and RuO2 appears near 2.45 Å, which can be attributed to the multiple scattering path Ru-N-Cu / Ru. Crucially, no strong Ru-Ru nearest neighbor peak or the oxide-specific Ru-O-Ru band was observed in Cu-ZIF8-Ru. This clearly indicates that the Ru atoms in Cu-ZIF8-Ru are in a highly dispersed state, most likely a single-atom Ru or a low-coordination structure. Furthermore, the Ru-N-Cu / Ru multiple scattering path obtained near 2.45 Å reveals that Ru and Cu are geometrically correlated through N, consistent with the proposed Cu-N-Ru bridging site.

[0061] The near-edge absorption threshold positions of Cu K-edge XANES spectra of Cu-ZIF8 and Cu-ZIF8-Ru are significantly higher than those of Cu foil (Ru0) but lower than those of CuO (Cu). 2+ () Figure 3 D), the white line intensity is similar to that of CuO. This indicates that Cu is predominantly in the +2 oxidation state in both Cu-ZIF8 and Cu-ZIF8-Ru, and the introduction of Ru did not reduce Cu. Notably, Cu-ZIF8-Ru shows a slight but discernible difference in energy and amplitude at the edges compared to Cu-ZIF8, suggesting that the local coordination of Cu sites and the ligand field are fine-tuned by Ru. This can be further analyzed by observing the EXAFS oscillation curves of the Cu K-edge in Cu-ZIF8 and Cu-ZIF8-Ru. Figure 3 The amplitudes of Cu-ZIF8 and Cu-ZIF8-Ru are significantly smaller than those of Cu foil and CuO, which is highly consistent with the fitted curves. This low amplitude characteristic indicates that the first coordination shell of Cu atoms is a low-coordination environment with a high degree of local disorder. This can be attributed to Cu-N coordination rather than Cu-Cu metal neighbor or Cu-O, thus ruling out the aggregation of metallic copper.

[0062] The Ru K-edge EXAFS Fourier transform spectra of Cu-ZIF8 and Cu-ZIF8-Ru show ( Figure 3In the F layer, Cu foil exhibits a Cu-Cu coordination peak near 2.21 Å, while CuO shows a Cu-O path characteristic at 1.56 Å. Both Cu-ZIF8 and Cu-ZIF8-Ru show a Cu-N first-shell peak near 1.56 Å. The slight shift in R-space between Cu-ZIF8-Ru and Cu-ZIF8 suggests a ligand field fine-tuning caused by Ru. Neither shows a Cu-Cu metallic peak, ruling out copper clusters. Notably, in the second shell, Cu-ZIF8 shows a Cu-N-Zn multiple scattering path near 2.54 Å; while Cu-ZIF8-Ru shows a Cu-N-Zn multiple scattering path near 2.57 Å, replacing part of the Cu-N-Zn signal, and the fit matches the experimental results well.

[0063] Although weak peaks in the second shells of Cu-ZIF8 and Cu-ZIF8-Ru were observed, the paths of Cu-N-Zn and Cu-N-Ru partially overlapped in the R-space, making it difficult to assign them solely based on amplitude. Considering the different responses of different scatterers in the k-space (heavy elements are stronger at higher k), WT-EXAFS analysis was further employed to simultaneously observe the shell location and scattering intensity distribution in the Rk plane to determine the source of the weak peak. This differs from the WT plots of Ru foil and RuO2 (…). Figure 3 In Cu-ZIF8-Ru, significant Ru-N hotspots are observed in the R-space region around 1–2 Å and the k-space region around 6–9 Å⁻¹, while no Ru-Ru or Ru-OR hotspots are observed in the high k-space region. Most importantly, weak hotspots appear in Cu-ZIF8-Ru in the R-space region around 2.6–2.9 Å and the k-space region around 7–10 Å⁻¹, which can be attributed to the multiple scattering path of Ru-N-Cu / Ru. This confirms that the first Ru shell of Cu-ZIF8-Ru is Ru-N with no metallic Ru-Ru neighbors, excluding metallic Ru clusters and oxides. The simultaneous appearance of multiple scattering in the second shell indicates that Ru is coupled to Cu through N, consistent with the conclusions inferred by UV-Vis, FTIR, and XPS.

[0064] Furthermore, the WT diagrams differ from those of Cu foil and CuO ( Figure 3 H), Cu-ZIF8 is located approximately 1.3–1.8 Å in R-space and 2–10 Å in k-space. -1 Significant Cu-N hotspots appear nearby; while in the vicinity of 2.8–3.0 Å in R space and 6–9 Å in k space... -1 The presence of hotspots in the vicinity can be attributed to multiple scattering paths of Cu-N-Zn in the second shell. Similar to Cu-ZIF8, Cu-ZIF8-Ru exhibits hotspots in the vicinity of 1.3–1.7 Å in R-space and 2–10 Å in k-space. -1The presence of significant Cu-N hotspots nearby indicates that the geometry of the first coordination shell of Cu-N was not disrupted after the introduction of Ru. Most importantly, the second shell hotspot of Cu-ZIF8-Ru is located approximately 2.8–3.0 Å in R-space and 7–10 Å in k-space. -1 The scattering is slightly enhanced in the vicinity, which can be attributed to the multiple scattering pathway of Cu-N-Ru. Since the atomic number of Ru is higher than that of Zn, its scattering is enhanced in the higher k region. This shift in k space directly confirms that Ru enters the second shell of Cu through the ligand N to form a heteronuclear metal Cu-N-Ru bridging site.

[0065] 3. Analysis of the multi-enzyme activity and mechanism of enhanced enzyme activity of Cu-ZIF8-Ru nanozymes (1) Multienzyme activity of Cu-ZIF8-Ru nanozymes To verify the multi-enzyme activity of Cu-ZIF8-Ru, 3,3',5,5'-tetramethylbenzidine (TMB), o-phenylenediamine (OPD), and 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) were used as chromogenic substrates to verify the POD, OXD, and GSH-Px-like enzyme activities of Cu-ZIF8-Ru.

[0066] Results analysis: like Figure 4 As shown in Figure A, the catalytic mechanism of various enzymatic activities of Cu-ZIF8-Ru is illustrated. To ensure consistent reaction conditions, a strong acid was added to terminate the reaction after the same reaction time. Figure 4 As shown in B-4C, Cu-ZIF8-Ru can oxidize TMB to blue oxTMB in both the presence and absence of hydrogen peroxide (H2O2), with a deeper blue color and stronger characteristic peaks in the presence of H2O2, indicating that Cu-ZIF8-Ru has good POD-like enzyme activity. Notably, Cu-ZIF8-Ru still oxidizes TMB to blue oxTMB in the absence of H2O2, demonstrating its intrinsic OXD-like activity. More importantly, under the same treatment, the characteristic peaks of Cu-ZIF8-Ru are more pronounced than those of Cu-ZIF8, confirming that Cu-ZIF8-Ru has stronger OXD-like and POD-like enzyme activities. This may be because the Cu-N-Ru heteronuclear metal bridging site in Cu-ZIF8-Ru facilitates electron transfer, thereby enhancing the enzyme activity of Cu-ZIF8-Ru. Cu-ZIF8-Ru in the absence of H2O2 (… Figure 4 (D) The solution can oxidize TMB, and the blue color of the solution deepens with increasing Cu-ZIF8-Ru concentration, indicating that the OXD-like and OPD-like enzyme activities of Cu-ZIF8-Ru nanoparticles are concentration-dependent. At a fixed concentration of 50 μg / mL... -1 Cu-ZIF8-Ru ( Figure 4 E), the color of the TMB solution deepens and the characteristic peak becomes stronger with increasing H2O2 concentration, indicating that the OXD-like and POD-like enzyme activities of Cu-ZIF8-Ru increase with increasing H2O2 concentration. Furthermore, Cu-ZIF8-Ru can oxidize OPD to yellow oxOPD in both the presence and absence of H2O2. Figure 4 F-4G), and the yellow color is deeper and the characteristic peaks are stronger in the presence of H2O2. Thanks to the high specific surface area and abundant active sites of Cu-ZIF8-Ru, the OPD probe showed similar results to the TMB probe under different concentrations of H2O2 and Cu-ZIF8-Ru treatment (F-4G). Figure 4 (H-4I), which further confirms that Cu-ZIF8-Ru has good OXD-like and OPD-like enzyme catalytic activities. These findings collectively demonstrate that Cu-ZIF8-Ru nanozymes possess good OXD-like and POD-like enzyme activities.

[0067] High levels of glutathione (GSH) can directly react with reactive oxygen species (ROS) through its reduced form, the active sulfhydryl group (-SH), and are one of the major antioxidants in bacteria. Under host stress, pathogenic bacteria maintain high levels of GSH by upregulating glutathione reductase, thereby protecting themselves from oxidative damage. Therefore, an effective GSH depletion strategy that disrupts the bacterial microenvironment balance and amplifies oxidative stress can significantly improve bactericidal efficacy. Notably, reports have confirmed that copper-based nanozymes possess good GSH-Px-like enzyme activity capable of consuming GSH. DTNB can react with GSH to generate 2-nitro-5-thiobenzoic acid (TNB-), and the absorbance at 412 nm can be measured to accurately calculate the remaining GSH concentration. Therefore, the GSH peroxidase (GSH-Px-like) activity of Cu-ZIF8-Ru was verified using a DNTB probe. The concentration of Cu-ZIF8-Ru was 50 μg / mL. -1 In a reaction system co-incubated with the same amount of GSH ( Figure 4 The characteristic peak at 412 nm slowly disappeared with increasing time, indicating that Cu-ZIF8-Ru can effectively consume GSH and exhibits good GSH-Px-like enzyme activity. When Cu-ZIF8-Ru reaches 100 μg / mL ( Figure 4 The GSH was consumed within only 30 minutes, further confirming that Cu-ZIF8-Ru has good GSH-Px-like enzyme activity.

[0068] In summary, Cu-ZIF8-Ru is a nanozyme with OXD-like, POD-like, and GSH-Px-like enzyme activities, and it has great potential in antibacterial activity and synergistic antibacterial effects. High levels of ROS generation are crucial for killing bacteria. Given the significant influence of H2O2 and dosage on Cu-ZIF8-Ru enzyme activity, ESR detection using 5,5-Dimethyl-1-pyrroline N-oxide (DMPO) and 2,2,6,6-Tetramethylpiperidine (TEMP) under different treatments further validated the types of reactive oxygen species generated by Cu-ZIF8-Ru. In the presence of the same concentration of H2O2, Cu-ZIF8-Ru produced a stronger ESR signal than Cu-ZIF8, with a four-line spectrum of 1:2:2:1. Figure 4 The presence of L indicates that Cu-ZIF8-Ru has a more efficient ability to generate •OH. This can be attributed to the electronic coupling effect of the heteronuclear metal Cu-N-Ru bridging sites in Cu-ZIF8-Ru, which lowers the potential barrier for pyrolysis. The photosensitizing effect of Ru(II) as a photosensitizer and the generation of singlet oxygen under light irradiation has been well confirmed, and the loading rate of Ru(II) in Cu-ZIF8-Ru is approximately 39%~49%. Under 660nm laser irradiation, Cu-ZIF8-Ru can generate a stronger ESR signal than Ru(II), and the four-line spectrum is 1:2:2:1 ( Figure 4 M), indicating that Cu-ZIF8-Ru has a more efficient generation process. 1 The ability of O2 to react may be due to the high specific surface area of ​​Cu-ZIF8-Ru and the presence of heteronuclear metal Cu-N-Ru bridging sites, which promote electron transfer under illumination and suppress excited-state recombination, thereby enhancing O2 reaction. 1 The generation of O2.

[0069] In summary, Cu-ZIF8-Ru exhibits a stronger ROS generation capacity than Ru(II) or Cu-ZIF8. These findings collectively suggest that Cu-ZIF8-Ru nanozymes have the potential to significantly enhance their antibacterial effects by synergistically generating ROS and disrupting the antioxidant barrier through multi-enzyme mimicry activities.

[0070] (2) Mechanism of Cu-ZIF8-Ru nanozymes enhancing enzyme activity To elucidate the mechanism and advantages of heteronuclear metal Cu-N-Ru bridging sites in enhancing the catalytic activity and ROS generation of Cu-ZIF8-Ru nanozymes, DFT calculations were performed. The essence of the catalytic reaction is the adsorption and desorption process of intermediates. Appropriate interactions between the metal sites and the substrate or intermediate are key to high catalytic activity. Modeling and simulation were performed based on the structure of ZIF8, and optimization was carried out based on the results of XAFS analysis.

[0071] Results analysis: The geometrically optimized structures of Cu-ZIF8 and Cu-ZIF8-Ru are shown in the figure. Figure 5 As shown in A-5B, Cu-ZIF8 exhibits a typical unsaturated Cu-N3 bond length of 1.976 Å and a bond angle of 110.148°. The introduction of Ru into Cu-ZIF8-Ru creates a heteronuclear Cu-N-Ru bridging site, leading to local geometric rearrangement. The Cu-N bond at the Cu-N-Ru bridging site in Cu-ZIF8-Ru changes from the equal-length Cu-ZIF8 to two inequivalent bonds of 1.808 Å and 1.840 Å, indicating an enhanced and geometrically asymmetric ligand field at the Cu site. The Ru-N bond length is 1.584 Å, significantly shorter than Cu-N, indicating stronger Ru coordination with N and tighter electronic coupling, consistent with XAFS, XPS, and FTIR analyses. Notably, the bond angle at the Cu-N-Ru bridging site significantly increases to 133.085° compared to Cu-N3, indicating a more open coordination space in the Cu neighborhood. This asymmetric Metal-N bond and more open reaction sites are more conducive to substrate adsorption and desorption as well as electron transfer. Moreover, the two sides of the asymmetry are equivalent to two channels, which better induce carrier splitting and achieve efficient enzyme catalytic performance.

[0072] To further evaluate the structural stability of Cu-ZIF8-Ru ( Figure 5 C), calculate the bond energies of Cu-N, Ru-N, and Cu-N-Ru bridging sites. The results show that the bond energies of Cu-N, Ru-N, and Cu-N-Ru bridging sites in Cu-ZIF8-Ru are all lower than those in the single-site model, with the Cu-N-Ru bridging site showing the most significant decrease from 85.14 kJ·mol⁻¹. -1 It decreased to 71.55 kJ·mol⁻¹ -1 Lower bond energies mean that bond length vibrations, bond angle opening, and electronic polarization are more likely to occur during the reaction, which can optimize the energy barriers of different reaction pathways to achieve efficient catalysis of the substrate. To better understand the influence of asymmetric Cu-N-Ru bridging sites on the electronic structure of Cu-ZIF8-Ru, the changes in partial density of states (PDOS) of Cu-ZIF8 and Cu-ZIF8-Ru were analyzed. Cu-ZIF8 has a very low total density of states near EF and exhibits a significant "quasi-bandgap" ( Figure 5 The contribution from Cu-ZIF8 mainly comes from the weak hybridization of Cu, N, and C, while the contributions from Zn and H are almost negligible. This indicates that Cu-ZIF8 has sparse electronic states, limited carrier density, and restricted charge mobility. Cu-ZIF8-Ru exhibits significant density-of-state filling and broadening on both sides of EF (…). Figure 5The total DOS is significantly increased (E). Ru undergoes strong hybridization with Cu and N near EF, forming continuous electron channels, accompanied by a shift of the d-band center towards EF (most pronounced in Cu). This indicates that the introduction of Ru constructs Cu-N-Ru bridging sites, enhancing the conductivity of Cu-ZIF8-Ru, making it easier for electron transfer to occur, and lowering the reaction barrier.

[0073] To visually reveal the modulation of the electronic structure of dissimilar metal bridging sites from space, the charge density difference and Bader charge were calculated. The Cu-ZIF8 differential charge density map shows the area near the Cu-N3 site ( Figure 5 F), electrons exhibit weak polarization between the imidazole ligand and Cu, and the charge distribution between Cu and the adjacent N is limited, indicating low charge polarizability at the Cu-N3 site. Unlike Cu-ZIF8, Cu-ZIF8-Ru shows extensive electron enrichment / depletion isosurfaces around the N at the Cu-N-Ru bridging site. Figure 5 Furthermore, the Ru side exhibits significant electron enrichment while the Cu side is electron-deficient, indicating the establishment of a directional electron transfer channel along Cu→N→Ru and enhanced electronic polarization. The electron deficiency at the Cu end and the electron enrichment at the Ru end enhance the adsorption and desorption of substrates by Cu-ZIF8-Ru, and lower the activation barrier of Cu-ZIF8-Ru for substrates. Corresponding Bader analysis shows that Cu loses electrons while Ru gains electrons in Cu-ZIF8-Ru (Cu gains electrons from Ru). The value of Ru increased from 0.59 eV to +1.42 eV; Ru increased from +1.86 eV; N increased from... Adjusted to 0.59eV The result (0.57 eV) reveals charge redistribution between Cu-N-Ru bridging sites. This is consistent with the results of XPS analysis, further validating the experimental results from theoretical calculations. The asymmetric Cu-N-Ru bridging sites establish directional electron channels and enhance electronic polarization, and through charge redistribution, achieve better adsorption and desorption, further reducing the reaction barrier and enhancing enzyme catalytic efficiency.

[0074] To further clarify the effect of the asymmetric Cu-N-Ru bridging site on the catalytic activity of Cu-ZIF8-Ru enzyme, the intermediate structure of Cu-ZIF8-Ru reacting with O2, H2O2, and GSH was optimized by DFT. Figure 5 H-5J) and proposed the corresponding reaction pathway to calculate its Gibbs free energy change ( Figure 5 K-5M). For example... Figure 5 As shown in K, from O2 adsorption, H2O2 transitions to In the formation of OH and H₂O, Cu-ZIF₈-Ru has a lower free energy than Cu-ZIF₈ at each key step, especially... O2→ H2O2 and The energy barrier reduction is most significant in the two steps from OH to H₂O. This indicates that the introduction of Ru makes the site more readily activated for O₂ and facilitates electron transfer, explaining the enhanced color development and ROS formation under H₂O₂-free conditions. However, in the reaction of Cu-ZIF₈-Ru with H₂O₂ ( Figure 5 L), from After H2O2 adsorption, O-O bond breaking occurs during the transition. O+ H2O intermediate towards O2 generation, Cu-ZIF8-Ru compared to Cu-ZIF8 OO fracture and The O2 formation process has a more negative free energy and a lower energy barrier, while... O→ The O2 channels are more open, facilitating the formation of Cu-ZIF8-Ru. 1 O2 provides thermodynamic support. A similar situation occurs in the reaction pathway of GSH adsorption in Cu-ZIF8-Ru. Figure 5 Compared to Cu-ZIF8, Cu-ZIF8-Ru exhibits a smoother and more efficient catalytic cycle for GSH. Specifically, it is... O+GSH→ OH+GS H2O + GSSG → GSSG, GSSG→GSSG+ In the three key hydrogen extraction, repositioning, and desorption reaction steps, Cu-ZIF8-Ru has a lower energy barrier and is more likely to occur than Cu-ZIF8. This can be attributed to the fact that the electron deficiency on the Cu side and the electron enrichment on the Ru side of the asymmetric Cu-N-Ru bridging site together lower the electron transfer barrier.

[0075] In summary, the Cu-ZIF8-Ru nanozyme utilizes the asymmetric Cu-N-Ru bridging site as the enzyme's active center. The Cu neighborhood creates a more open coordination space, and the electron deficit provides more open active reaction sites. Meanwhile, the electron enrichment on the Ru side promotes electron carrier splitting, resulting in highly efficient enzyme catalytic performance. Furthermore, by modulating the d-band center to shift towards the EF direction, electron transfer is facilitated, and the reaction barrier is lowered. The establishment of a Cu→N→Ru directional electron channel enhances electronic polarization, leading to better adsorption and desorption, further enhancing the enzyme's catalytic efficiency.

[0076] Example 2 This embodiment verifies the biosafety and efficacy of Cu-ZIF8-Ru nanozyme in killing multidrug-resistant bacteria in vitro.

[0077] 1. Biosafety of Cu-ZIF8-Ru nanozymes Cu-ZIF8-Ru with copper contents of 10%, 20%, and 30% was synthesized and tested in SV-HUC-1 and HUVEC cells (density 4 × 10⁻⁶). 4 100 μL of Cu-ZIF8-Ru with different copper contents (concentration range of 0~400 μg / mL) was added to each well of a 96-well plate and incubated for 12 h. 20 μL of CCK8 was added to each well and incubated for 2 h, followed by cell viability measurement using a microplate spectrophotometer. After the above screening, the Cu-ZIF8-Ru with the safest copper concentration range was selected for further verification of its biosafety. The cells were grouped as follows: Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. SV-HUC-1 cells were quantitatively incubated with Cu-ZIF8-Ru in 96-well plates for 5 h. Cells in the Laser group were then exposed to a power of 100 mW / cm². 2 Cells were incubated in a 660 nm laser for 10 min. 20 μL of CCK8 was added to each well and incubated for 2 h. Cell viability was then measured using a microplate spectrophotometer.

[0078] Results analysis: like Figure 6 As shown in Figure A, different proportions of Cu (10%, 20%, and 30%, respectively) and different concentrations (0–400 μg / mL) were synthesized. -1 Co-incubation of Cu-ZIF8-Ru with normal urothelial cells SV-HUC-1 maintained cell viability at 90%–100% throughout the process, with no significant dose-dependent toxicity observed. Compared to SV-HUC-1, human umbilical vein endothelial cells (HUVECs) were incubated at 200 μg / mL. -1 A visible decrease in activity began to appear. Figure 6 (B) The effect slightly increased with increasing copper content, suggesting a certain inhibitory effect on endothelial cells at extremely high doses. This may be related to the more active metabolism and higher sensitivity to ROS in HUVECs. Therefore, a Cu content of 20% and a concentration range of 0–200 μg / mL were selected. -1 Cu-ZIF8-Ru can be used for antibacterial therapy while ensuring biosafety and maintaining Cu levels. 2+ Controlled release in bacteria. Next, the CCK-8 assay was used to detect SV-HUC-1 at concentrations ranging from 0 to 200 μg / mL. -1 The survival rate of Cu-ZIF8-Ru was determined by setting up different groups and laser irradiation groups (660nm, 100mW / cm). 2(10 min) to investigate potential toxicity. Cu-ZIF8-Ru was used for quantitative comparison of concentrations ranging from 0 to 200 μg / mL. -1 The effects of Ru(II), Cu-ZIF8 and Cu-ZIF8-Ru on SV-HUC-1 Figure 6 C), the near 100% survival of all three indicates that Cu-ZIF8-Ru exhibits good biocompatibility when incubated alone. However, after 660nm laser irradiation, the effects of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru on the activity of SV-HUC-1 were not significantly different from the control group. Figure 6 (D) This further confirms that Cu-ZIF8-Ru exhibits high biocompatibility within a concentration range of 0–200 μg mL⁻¹, and that light exposure does not significantly increase toxicity. This provides a reference for subsequent administration of Cu-ZIF8-Ru via bladder instillation for the treatment of urinary tract infections.

[0079] 2. The bactericidal effect of Cu-ZIF8-Ru nanozyme against multidrug-resistant bacteria (1) Antibacterial activity: To verify the antibacterial activity of Cu-ZIF8-Ru against multidrug-resistant Escherichia coli (E. coli). The groups were Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Ru(II)+Laser, Cu-ZIF8+Laser, and Cu-ZIF8-Ru+Laser. Multidrug-resistant E. coli was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL. Different concentration series (0, 12.5, 25, 50, 75, 100, 150, 200 μg / mL, quantified using Cu-ZIF8-Ru) were prepared for each group. Bacterial suspensions were added to 96-well plates along with corresponding concentrations of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru, and incubated for 5 h at pH 5.5 and H2O2. The Laser group bacteria were then exposed to a power of 1 W / cm². 2The cells were incubated in a 660 nm laser for 10 min. After 12 h of incubation, Alamar Blue reagent (10% by volume) was added to each well, and the cells were incubated for another 4 h in a constant temperature incubator. The bacterial activity was determined by recording and observing the color changes with a camera, and the fluorescence values ​​of each group were measured using a microplate spectrophotometer (excitation wavelength: 540 nm, emission wavelength: 590 nm) to evaluate the effect of each group on the activity of multidrug-resistant Escherichia coli and to confirm the optimal antibacterial incubation conditions. Control group, Ru(II) group, Cu-ZIF8 group, Cu-ZIF8-Ru group, Laser group, Ru(II)+Laser group, Cu-ZIF8+Laser group, and Cu-ZIF8-Ru+Laser group were set up to compare the contribution of different systems to the antibacterial efficacy of MDR E. coli.

[0080] Results analysis: like Figure 6 As shown in Figure E, the color of the treated wells of MDR E. coli changed from pink (metabolic activity) to blue-purple (metabolic inhibition / death) with increasing Cu-ZIF8-Ru nanozyme concentration. Under no light, the antibacterial efficiency of Cu-ZIF8-Ru was significantly higher than that of Cu-ZIF8 and Ru(II). Under light, all three showed enhanced antibacterial activity, but Cu-ZIF8-Ru+Laser showed the greatest increase, and the color change was more significant at high concentrations. This indicates that Cu-ZIF8-Ru nanozyme possesses broad-spectrum and highly efficient antibacterial potential. Figure 6 F-6G), and the quantitative fluorescence results further confirmed this conclusion.

[0081] (2) Intracellular reactive oxygen species (ROS) assay: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium to the logarithmic growth phase. The bacterial concentration was adjusted to approximately 1 × 10⁶ CFU / mL using the dilution method and incubated for 5 h in an environment of pH 5.5 and H₂O₂. The bacteria were divided into Control, Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Laser, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. Bacterial solutions were added to 24-well plates and incubated with the same concentration of 50 μg / mL (quantified as Cu-ZIF8-Ru) of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru for 5 h. The Laser group bacteria were then exposed to a power of 1 W / cm². 2 The bacteria were incubated in a 660 nm laser for 10 min. After 2 h of incubation, they were treated with a 2′,7′ dichlorodihydrofluorescein diacetate (DCFH-DA) probe and incubated in a 37 °C oven for 20 min. After incubation, the solution was washed three times with PBS, and images of the stained bacteria were obtained using a fluorescence microscope.

[0082] Results analysis: like Figure 6 As shown in Figure H, the control and laser-treated cells showed almost no fluorescence; Ru(II) and Cu-ZIF8 produced limited green signals, while Cu-ZIF8-Ru significantly enhanced them. Cu-ZIF8-Ru exhibited the strongest bright fluorescence in MDR E. coli after laser treatment, far exceeding that of the Ru(II)+Laser and Cu-ZIF8+Laser groups, demonstrating that Cu-ZIF8-Ru nanozymes with asymmetric heterometallic Cu-N-Ru bridging sites can trigger a more vigorous ROS burst within the bacteria. Figure 6 As shown in O, this result was further verified by quantitative calculations.

[0083] (3) Bacterial live / dead bacteria test: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL was incubated for 5 h at pH 5.5 and H2O2. The cells were divided into Control, Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Laser, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. Bacterial culture was added to 24-well plates and incubated with the same concentration (50 μg / mL, quantified as Cu-ZIF8-Ru) of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru for 5 h. After incubation, the Laser group bacteria were exposed to a power of 1 W / cm². 2 The bacteria were incubated in a 660nm laser for 10 minutes. After 12 hours of incubation, SYTO-9 and PI were added to the bacteria, and the mixture was incubated at 37°C for another 20 minutes. After incubation, images of the stained bacteria were obtained using a fluorescence microscope.

[0084] Results analysis: like Figure 6 As shown in Figure I, in the control group and the laser-only group, the field of view was almost entirely occupied by green signals, indicating that the bacteria were basically alive. The Ru(II) group or the Cu-ZIF8 group alone only showed sporadic red dot signals, indicating limited bactericidal effect. In contrast, Cu-ZIF8-Ru significantly increased the proportion of red fluorescence, showing that it could cause membrane damage even without laser treatment. In the Cu-ZIF8-Ru+Laser group, green fluorescence almost disappeared while red fluorescence was dense and patchy, indicating that membrane damage and irreversible bacterial death were most significant.

[0085] (4) Bacterial plating test: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6CFU / mL. The groups were Control, Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Laser, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. Bacterial culture was added to each well of a 24-well plate along with 50 μg / mL (quantified as Cu-ZIF8-Ru) of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru, respectively. The plates were incubated at pH 5.5 and H2O2 for 5 h. After incubation, the Laser group bacteria were exposed to a power of 1 W / cm². 2 The bacteria were incubated in a 660nm laser for 10 minutes. After 12 hours of incubation, the bacterial cultures from the eight groups were diluted 10 times. 4 Each group of 40 μL bacterial culture was spread onto an agar plate and incubated at 37°C for 15 hours. The number of bacterial clones was calculated using ImageJ, and the survival rate of the target bacteria was also calculated.

[0086] Results analysis: like Figure 6 As shown in Figure J, both the control group and the laser-only group formed dense and uniform colonies, indicating essentially no antibacterial effect; Ru(II) or Cu-ZIF8 treatment alone only slightly reduced the colony count. In contrast, Cu-ZIF8-Ru significantly reduced colony density under light-free conditions, indicating that Cu-ZIF8-Ru can significantly inhibit MDR E. coli even without light. Particularly noteworthy is the near disappearance of MDR E. coli colonies in the Cu-ZIF8-Ru+Laser group. This demonstrates that Cu-ZIF8-Ru can achieve strong bactericidal and growth-inhibiting effects under laser light irradiation. Figure 6 As shown in Figure P, the quantitative calculation of bacterial clones on plate further verifies that Cu-ZIF8-Ru nanozyme can significantly inhibit the activity of MDR E. coli to achieve a better bactericidal effect.

[0087] (5) Changes in bacterial morphology: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL was incubated for 5 h at pH 5.5 and H2O2. The cells were divided into Control, Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Laser, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. Bacterial culture was added to 24-well plates and incubated with the same concentration (50 μg / mL, quantified as Cu-ZIF8-Ru) of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru for 5 h. After incubation, the Laser group bacteria were exposed to a power of 1 W / cm². 2The bacteria were incubated in a 660 nm laser for 10 min. After 7 h of incubation, the bacterial cultures from each group were collected, washed three times with PBS, immediately fixed with 2.5% glutaraldehyde for 30 min, and then subjected to gradient ethanol dehydration treatment before the morphological changes of the bacteria were observed using a scanning electron microscope.

[0088] Results analysis: like Figure 6 As shown in K, in the control group and the laser-only group, MDR E. coli maintained a typical rod / short rod morphology, with smooth cell surfaces, intact boundaries, and no obvious depressions or cracks, indicating that the cell wall / membrane structure was basically intact. After treatment with Ru(II) or Cu-ZIF8 alone, sporadic wrinkling and slight depressions appeared on the cell surface, indicating that there was only limited membrane damage. In contrast, Cu-ZIF8-Ru showed significantly stronger structural morphological destruction, with a large number of pits, grooves, and collapses on the cell surface (red arrows). Some cells blistered and deformed, indicating a significant increase in membrane permeability and leakage of intracellular substances. It is worth noting that this damage was further aggravated in the Cu-ZIF8-Ru+Laser group: bacteria generally showed large-scale membrane tears, severe wrinkling, and "hollowing out" characteristics, indicating that the bacterial cell wall membrane was irreversibly damaged by the synergistic effect of Cu-ZIF8-Ru nanozyme and light irradiation.

[0089] (6) Surface adhesion of Cu-ZIF8-Ru: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL was incubated at pH 5.5 and H2O2 for 5 h. The cells were divided into Control and Cu-ZIF8-Ru groups. Bacterial culture was added to 24-well plates and incubated with 50 μg / mL Cu-ZIF8-Ru for 5 h. The Laser group bacteria were then exposed to a power of 1 W / cm². 2 The bacteria were incubated in a 660 nm laser for 10 minutes. After 7 hours of incubation, the bacterial cultures from each group were collected, immediately fixed with 2.5% glutaraldehyde for 30 minutes, and then subjected to gradient ethanol dehydration treatment. The morphology of Cu-ZIF8-Ru and the bacterial surface was then observed using transmission electron microscopy.

[0090] Results analysis: like Figure 6 The control group of E. coli, as shown in Figure L, consisted of rod-shaped cells with intact outlines and smooth surfaces. In contrast, the Cu-ZIF8-Ru treatment primarily adhered to the surface of MDR E. coli. This can be attributed to the fact that bacteria contain a large amount of negatively charged lipopolysaccharides and peptidoglycans in their cell walls and cell membranes, while Cu-ZIF8-Ru, being positively charged, preferentially targets and adheres to the bacterial surface.

[0091] (7) Changes in bacterial ultrastructure: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 The bacteria were incubated at CFU / mL in a pH 5.5, H₂O₂ environment for 5 h. The groups were designated Control and Cu-ZIF₈-Ru + Laser. Bacterial suspensions were added to 24-well plates, and the control group was incubated with 50 μg / mL Cu-ZIF₈-Ru for 5 h. The Laser group was then exposed to a 1 W / cm² laser at a wavelength of 660 nm for 10 min. After 7 h of incubation, the bacterial suspensions from each group were collected, washed three times with PBS, immediately fixed with 2.5% glutaraldehyde for 30 min, and subjected to graded ethanol dehydration. The precipitates were collected, frozen, and sectioned. Transmission electron microscopy was used to observe the ultrastructural changes of the bacteria after Cu-ZIF₈-Ru treatment.

[0092] Results analysis: like Figure 6 As shown in M, the control group bacteria had good cell morphology, dense cytoplasm, and intact cell wall membrane, while the MDR E. coli treated with Cu-ZIF8-Ru showed membrane undulation and rupture, as well as sparse cytoplasm and vacuolation. This directly demonstrates that the multidrug-resistant bacteria treated with Cu-ZIF8-Ru suffered severe membrane barrier damage and loss of cytoplasmic contents.

[0093] (8) Intracellular elemental distribution of bacteria: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL was incubated at pH 5.5 and H2O2 for 5 h. The cells were divided into Control and Cu-ZIF8-Ru groups. Bacterial culture was added to 24-well plates and incubated with 50 μg / mL Cu-ZIF8-Ru for 5 h. The Laser group bacteria were then exposed to a power of 1 W / cm². 2 The bacterial culture was incubated in a 660nm laser for 10 minutes. After 7 hours of incubation, the bacterial culture from each group was collected, washed three times with PBS, immediately fixed with 2.5% glutaraldehyde for 30 minutes, and then subjected to gradient ethanol dehydration treatment before collecting the bacterial culture. The bacterial samples were then dropped onto a copper mesh support, dried at room temperature, and directly used for TEM-EDS testing.

[0094] Results analysis: like Figure 6As shown in Figure N, the Cu-ZIF8-Ru treatment group exhibited a strong, ring-shaped Cu mapping along the cytoplasmic edge in MDR E. coli bacteria; Zn signaling was also enriched at the periphery of the cytoplasm; while the Ru signal was generally weak, it was discernibly co-localized with Cu and Zn on the cell surface. Simultaneously, the O signal was relatively weakened in the membrane region, suggesting local membrane disruption. Clearly, the Cu-ZIF8-Ru nanozyme accelerated Zn infiltration after disrupting the MDR E. coli bacterial cell membrane. 2+ Cu 2+ It enters the bacterial cytoplasm, causing an intracellular copper ion overload.

[0095] (9) Bacterial ATP content: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL was incubated for 5 h at pH 5.5 and H2O2. The cells were divided into Control, Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Laser, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. Bacterial culture was added to 24-well plates and incubated with the same concentration (50 μg / mL, quantified as Cu-ZIF8-Ru) of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru for 5 h. After incubation, the Laser group bacteria were exposed to a power of 1 W / cm². 2 The bacterial culture was incubated in a 660 nm laser for 10 minutes. After 7 hours of incubation, the treated bacterial cultures from each group were collected, and the membranes were repeatedly frozen and thawed at -80°C before centrifugation to collect the supernatant. An ATP content detection kit was added to the supernatant, and the mixture was incubated at 37°C for 20 minutes. The leakage of ATP was quantitatively analyzed by measuring the fluorescence intensity using a microplate spectrophotometer.

[0096] Results analysis: like Figure 6 As shown in Q, after treatment of MDR E. coli with Cu-ZIF8-Ru nanozyme, the Cu-ZIF8 group reduced the intracellular ATP content of bacteria compared with the control group and Ru(II) group. The Cu-ZIF8-Ru group showed the largest reduction and further aggravated energy depletion after laser irradiation, indicating that bacterial respiration and metabolism were inhibited after Cu-ZIF8-Ru treatment.

[0097] (10) Changes in bacterial membrane potential: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6CFU / mL was incubated for 5 h at pH 5.5 and H2O2. The cells were divided into Control, Ru(II), Cu-ZIF8, Cu-ZIF8-Ru, Laser, Ru(II) + Laser, Cu-ZIF8 + Laser, and Cu-ZIF8-Ru + Laser. Bacterial culture was added to 24-well plates and incubated with the same concentration (50 μg / mL, quantified as Cu-ZIF8-Ru) of Ru(II), Cu-ZIF8, and Cu-ZIF8-Ru for 5 h. After incubation, the Laser group bacteria were exposed to a power of 1 W / cm². 2 Incubate in a 660nm laser for 10 minutes. After 7 hours of incubation, collect the bacterial culture from each group and add the DiSC3(5) probe to the bacteria. Incubate in a 37℃ constant temperature incubator for 20 minutes. Use a microplate spectrophotometer to measure the fluorescence value of each group (excitation wavelength: 622nm, emission wavelength: 670nm) to evaluate the degree of membrane potential depolarization of different treatment groups.

[0098] Results analysis: like Figure 6 As shown in Figure R, after treatment of MDR E. coli with Cu-ZIF8-Ru nanozymes, the DISC3(5) fluorescence intensity of the Cu-ZIF8 group was slightly higher than that of the control group and the Ru(II) group. The Cu-ZIF8-Ru group showed the largest increase, and the bacterial membrane potential depolarization was further aggravated after laser irradiation, indicating that the membrane potential collapse was most severe in the Cu-ZIF8-Ru group and the Cu-ZIF8-Ru+Laser group. This proves that the bacteria underwent membrane potential collapse after Cu-ZIF8-Ru treatment, thereby changing the membrane permeability, which is conducive to the further accumulation of metal ions in the bacterial cytoplasm.

[0099] 3. The bactericidal mechanism of Cu-ZIF8-Ru nanozyme against multidrug-resistant bacteria (1) Bacterial transcriptome analysis: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL and incubated for 5 h at pH 5.5 and H2O2. Grouped as Control and Cu... 2+ Cu-ZIF8-Ru and Cu-ZIF8-Ru+Laser were used, and bacterial culture was added to each well of a 24-well plate along with the same concentration of 15 μg / mL (using Cu... 2+ (Quantitative) Cu 2+ After incubation with Cu-ZIF8-Ru and Cu-ZIF8-Ru+Laser for 5 hours, the bacteria in the Laser group were exposed to a power of 1W / cm². 2The bacteria were incubated in a 660nm laser for 10 minutes. After 5 hours of incubation, the treated bacterial cultures from each group were collected and immediately frozen in liquid nitrogen before being sent to Shanghai Meiji Pharmaceutical Technology Co., Ltd. for prokaryotic transcriptome sequencing, including RNA extraction, sequencing, and preliminary analysis. RNA-seq paired-end sequencing was performed using Illumina NovaSeqXplus (Illumina Inc., San Diego, CA, USA). Bioinformatics analysis was performed using data generated by the Illumina platform. In addition to the default RSEM (http: / / deweylab.github.io / RSEM / ), Kallisto (https: / / pachterlab.github.io / kallisto / ) and Salmon (https: / / combine-lab.github.io / salmon / ) were used to calculate expression levels. The selection criteria for differentially expressed genes (DEGs) were set as |log2FoldChange|>1 and padj<0.05. Functional annotation clustering was achieved using the Gene Ontology (GO) database and the Kyoto Encyclopedia of Genes and Genomes (KEGG) database.

[0100] Results analysis: Cu-ZIF8-Ru group ( Figure 7 A), Cu-ZIF8-Ru+Laser group ( Figure 7 B) Compared to Cu 2+ The group showed a large number of DEGs. This result indicates that Cu-ZIF8-Ru significantly enhances Cu... 2+ The role of MDR E. coli in regulating Cu-ZIF8-Ru under illumination compared to free Cu 2+ The antibacterial activity is broader. Based on this, further GO enrichment analysis was performed on these DEGs, focusing on key pathways such as metal ion response, redox processes, bacterial cell membrane synthesis, and energy metabolism, in order to elucidate the synergistic effect of Cu-ZIF8-Ru-induced excess ROS and Cu. 2+ Overload plays a dominant role in the sterilization mechanism.

[0101] First, comparing Cu-ZIF8-Ru vs Cu 2+ Cu-ZIF8-Ru+Laser vs Cu 2+ A large number of DEGs were analyzed for GO enrichment to identify key biological processes affected. Cu-ZIF8-Ru vs Cu 2+ The upregulated DEGs are mainly enriched in protein / amino acid and carboxylic acid metabolism, biosynthesis, sulfur-containing compound biosynthesis, and cytoplasmic pathways. Figure 7C), simultaneously, enhanced pathways such as inorganic anion transmembrane transport and ion binding / redox activity are observed. This confirms that Cu-ZIF8-Ru, compared to free Cu, exhibits improved performance. 2+ It can enhance metal stress and oxidative stress in MDR E. coli and initiate a wide range of stress- and repair-oriented metabolic compensation, particularly increased biosynthesis of sulfur-containing compounds. This may be related to the presence of Cu in MDR E. coli. 2+ Overload is related to insufficient synthesis of sulfur-containing compounds. Cu-ZIF8-Ru vs Cu 2+ The significantly downregulated DEGs were mainly enriched in flagellar assembly, motility, ABC transporters, and transmembrane transport. Figure 7 D), simultaneously, metal ion responses and efflux, as well as downregulation of TCA cycle pathways, were observed. This confirms that Cu-ZIF8-Ru, compared to free Cu, exhibits... 2+ It significantly inhibits bacterial motility, migration, nutrient and metal transport, causing irreversible exhaustion of energy metabolism and weakening metal efflux and tolerance pathways. This can be attributed to the severe cell membrane damage induced by Cu-ZIF8-Ru in MDR E. coli and the increased intracellular Cu. 2+ Overload hinders the TCA cycle.

[0102] Furthermore, Cu-ZIF8-Ru+Laser vs Cu 2+ In addition to continuing the metabolic compensation mentioned above, the upregulation of DEGs ( Figure 7 E), the enrichment of pathways such as ribosomes, iron-sulfur cluster protein assembly, sulfur-related metabolism, and metal binding is more prominent. This further indicates that MDRE.coli is forced to enhance related biosynthesis and repair, suggesting more severe oxidative damage. Cu-ZIF8-Ru+Laser vs Cu 2+ The downregulation of major DEG enrichment pathways further confirms that Cu-ZIF8-Ru reduces bacterial flagella-related motility, metal ion transmembrane transport, membrane component and transmembrane transport complex functions after laser irradiation. Figure 7 The study found that Cu-ZIF8-Ru enhanced ROS stress after laser irradiation, leading to more significant ion homeostasis imbalance and chemotactic inhibition. This indicates that Cu-ZIF8-Ru enhances ROS stress and more deeply disrupts bacterial motility and transmembrane homeostasis, explaining its stronger bactericidal and biofilm-inhibiting effects.

[0103] After enrichment at the GO pathway level, a representative gene set was used to validate the above mechanism and compare the effects of different treatments on MDR E. coli gene expression. Figure 7 As shown in G, key gene clusters are listed according to functional regions, with colors ranging from red (upregulated) to blue (downregulated). Compared to the control group and free Cu... 2+ Cu-ZIF8-Ru has been significantly upregulated, Cu 2+Upregulation of efflux genes (copA, cueO, cusC, cusA) indicates the presence of Cu in MDR E. coli cells. 2+ Overload; while Zn 2+ Downregulation of uptake genes (znuA, znuB) and Zn 2+ Upregulation of efflux genes (znpA, znpT) indicates the presence of Zn in MDR E. coli cells. 2+ Overload was observed, consistent with TEM-EDS findings. Simultaneously, upregulation of genes related to cell wall membrane biosynthesis and permeability pointed to Cu-ZIF8-Ru disrupting the cell wall membrane barrier and causing membrane structural remodeling. Concurrently, the overall expression of marker genes for oxidative stress, antioxidant responses, DNA damage responses, and lipid peroxidation (LPO) was elevated, demonstrating intracellular ROS accumulation in MDR E. coli and causing damage to the membrane lipid layer. Downregulation of genes related to nutrient transporters and electron transport chains involved in energy and material transport, and decreased expression of TCA cycle multienzyme genes revealed energy suppression, confirming a state of energy starvation in the cells. Notably, repair pathways such as Fe-S cluster biosynthesis, thio metabolism / lipoic acid synthesis, and protein lipoylation were compensatorily upregulated, consistent with Cu-ZIF8-Ru disruption of the cell wall membrane barrier and subsequent remodeling. 2+ Overload-induced ROS preferentially disrupts Fe-S protein synthase and the respiratory electron transport chain. The addition of laser treatment further exacerbates this trend, resulting in stronger stress and repair, and weaker transport and energy chains, exhibiting typical Cu characteristics. 2+ Overload synergistic amplification of ROS leads to an imbalance between energy supply and demand, further exacerbating bacterial oxidative stress damage, thereby enhancing antibacterial and bactericidal effects.

[0104] (2) Bacterial pyruvate dehydrogenase (PDH) activity: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL and incubated for 5 h at pH 5.5 and H2O2. Grouped as Control and Cu... 2+ Cu-ZIF8-Ru and Cu-ZIF8-Ru+Laser were used, and bacterial culture was added to each well of a 24-well plate along with the same concentration of 15 μg / mL (using Cu... 2+ (Quantitative) Cu 2+ After incubation with Cu-ZIF8-Ru and Cu-ZIF8-Ru+Laser for 5 hours, the bacteria in the Laser group were exposed to a power of 1W / cm². 2 The bacteria were incubated in a 660nm laser for 10 minutes. After 5 hours of incubation, the treated bacterial cultures from each group were collected, and the membranes were repeatedly broken by freeze-thaw cycles at -80℃. The supernatants from each group were then collected by centrifugation. The pyruvate dehydrogenase (PDH) content was quantitatively analyzed by adding the PDH to the supernatants using a pyruvate dehydrogenase activity assay kit and measuring the absorbance at 605nm using a microplate spectrophotometer.

[0105] Results analysis: PDH activity was observed in the control group and Cu. 2+ The activity decreased sequentially from group A to group B, and then from group C to group D, with group C having the lowest activity. Figure 7 This trend is consistent with the results observed in GO / KEGG analysis, which showed inhibition of the TCA cycle / electron transport chain, membrane potential depolarization, and decreased ATP levels. This indicates that Cu-ZIF8-Ru effectively blocks the TCA cycle, and the inhibitory effect is further amplified after laser irradiation.

[0106] (3) Bacterial lipid peroxidation level: Multidrug-resistant Escherichia coli (E. coli) was cultured in LB liquid medium to the logarithmic growth phase. The bacterial concentration was adjusted to approximately 1×10⁶ CFU / mL using the dilution method and incubated for 5 h in an environment of pH 5.5 and H₂O₂. The samples were grouped as Control and Cu. 2+ Cu-ZIF8-Ru and Cu-ZIF8-Ru+Laser were used, and bacterial culture was added to each well of a 24-well plate along with the same concentration of 15 μg / mL (using Cu... 2+ (Quantitative) Cu 2+ After incubation with Cu-ZIF8-Ru and Cu-ZIF8-Ru+Laser for 5 hours, the bacteria in the Laser group were exposed to a power of 1W / cm². 2 The bacterial culture was incubated in a 660 nm laser for 10 min. After 5 h of incubation, the bacterial culture from each group was collected, and the membrane was repeatedly frozen and thawed at -80 °C before centrifugation to collect the supernatant. Malondialdehyde (MDA) was added to the supernatant of each group, and the absorbance at 532 nm was measured using a microplate spectrophotometer to quantitatively analyze the MDA content and assess the lipid peroxidation level.

[0107] Results analysis: The MDA content in the Cu-ZIF8-Ru group was significantly higher than that in the free Cu group. 2+ Compared with the control group, the Cu-ZIF8-Ru+Laser group had the highest ( Figure 7 (I) This directly proves that Cu-ZIF8-Ru leads to a sustained increase in membrane lipid peroxidation in MDR E. coli. In summary, Cu-ZIF8-Ru can disrupt the MDR E. coli cell wall membrane, inducing LPO and blocking the TCA cycle and respiratory chain function, similar to the mechanism of copper death in eukaryotic cells, indicating that Cu-ZIF8-Ru induces copper-like death processes in bacteria.

[0108] Example 3 This embodiment verifies the in vivo antibacterial effect of Cu-ZIF8-Ru nanozyme hydrogel on urinary tract infections caused by multidrug-resistant bacteria.

[0109] 1. Preparation of Cu-ZIF8-Ru nanozyme thermosensitive hydrogel Under nitrogen protection, a PLGA-PEG-PLGA triblock copolymer was prepared by ring-opening polymerization of D,L-lactide (LA) and glycolide (GA) using polyethylene glycol (PEG) as the initiator and Sn(Oct)₂ as the catalyst. The mass ratio of (LA+GA) / PEG was 2:1, and the molar ratio of LA / GA was 7:1. Briefly, 5.02 g of PEG1500 was degassed under nitrogen and stirred at 150 °C for 2 h. Then, GA (1.05 g, 9 mmol) and LA (9.0 g, 62.5 mmol) were added to a three-necked flask and maintained under nitrogen for 0.5 h. Then, 30 μL of Sn(Oct)₂ was added. The mixture was reacted at 150 °C for 10 h under nitrogen protection. The resulting solution was immediately poured into deionized water at 4 °C and stirred overnight. Then, the product was heated three times to 80°C in a water bath to remove unreacted monomers and water-soluble low-molecular-weight byproducts, yielding PLGA-PEG-PLGA hydrogel. Cu-ZIF8-Ru and PLGA-PEG-PLGA were mixed at a volume ratio of 1:3 and freeze-dried to obtain the product Cu-ZIF8-Ru-Gel. Figure 8 As shown in Figure B, Cu-ZIF8-Ru@Gel exhibits a significant viscosity peak around 37℃, indicating that loading Cu-ZIF8-Ru nanozymes did not alter its thermosensitive gel properties and even enhanced its density. Figure 8 C visually demonstrates that the phase transition window of Cu-ZIF8-Ru@Gel matches the body temperature of the bladder, proving that PLGA-PEG-PLGA-loaded Cu-ZIF8-Ru possesses thermogel properties and good injectability.

[0110] 2. ICG-labeled Cu-ZIF8-Ru@Gel bladder instillation sustained-release experiment: Six female C57BL / 6 mice (Xiao Hei) were prepared, aged 6-8 weeks, and deprived of water for 4 hours. They were divided into two groups: Cu-ZIF8-Ru and Cu-ZIF8-Ru@Gel. 50 μL of ICG-labeled Cu-ZIF8-Ru and Cu-ZIF8-Ru@Gel solutions were instilled into the bladders of C57BL / 6 mice via catheter, followed by water intake 2 hours later. Fluorescence distribution in the mice was recorded at 0.5, 1.5, 2, 3, 4, 6, 8, and 10 hours using an IVISLumina III in vivo imaging system (PerkinElmer, USA).

[0111] Results analysis: like Figure 8As shown in Figure D, the fluorescence signal in the bladder area after ICG-labeled Cu-ZIF8-Ru@Gel instillation disappeared after 10 hours, indicating good retention in the bladder; while the fluorescence signal of Cu-ZIF8-Ru completely disappeared in the bladder area after 3 hours. The fluorescence decay curve further confirms that Cu-ZIF8-Ru@Gel hydrogel can significantly prolong the residence time in the bladder. Figure 8 E), Cu-ZIF8-Ru@Gel has the potential to be used as a bladder instillation drug for the treatment of urinary tract infections.

[0112] 3. Recurrent urinary tract infection model: Thirty-six female C57BL / 6 mice (Black C57BL / 6) were prepared, aged 6-8 weeks. The mice were deprived of water for 4 hours before the experiment. They were grouped as follows: Uninfection, control, Cu-ZIF8, Cu-ZIF8-Ru, Cu-ZIF8-Ru-Gel, and Cu-ZIF8-Ru@Gel+Laser (n=6). Multidrug-resistant *E. coli* was cultured in LB broth until the logarithmic growth phase, and the bacterial concentration was adjusted to approximately 1×10⁻⁶ using the dilution method. 6 CFU / mL.

[0113] like Figure 8 As shown in Figure A, mice were first anesthetized intraperitoneally and their abdomens were shaved. Next, 50 μL of bacterial suspension (1 x 10⁻⁶) was injected into the bladder via the urethra using a soft tubing connected to a 1 mL syringe. 6 After standing for 30 seconds, the catheter was slowly removed, and the nude mice were allowed to recover before being returned to their cages. Water was restored 2 hours later. The infection was repeated 3 times every 4 days. Each day, 50 μL (quantified as Cu-ZIF8-Ru, 80 μg / mL) of Cu-ZIF8, Cu-ZIF8-Ru, and Cu-ZIF8-Ru-Gel were administered via bladder irrigation. One hour later, the bladder of mice in the Laser group was exposed to a 660 nm laser at a power of 1 W / cm² for 10 minutes. After 3 treatments, blood was collected from each group of mice, and the mice were euthanized by cervical dislocation. Bladders, kidneys, and other vital organs were collected. The collected bladders and kidneys were photographed and recorded. The bladders and kidneys were then cut in half; one half was stained for tissue sectioning, and the other half was assembled, homogenized, and added to LB broth. The cultures were incubated at 37°C for 8 hours. After incubation, the bacterial cultures were plated and incubated at 37°C for 15 hours. The number of bacterial clones was calculated using ImageJ, and the survival rate of bacteria in the bladder and kidneys was also calculated.

[0114] Results analysis: After treatment, bladder tissue samples were collected from each group. The Control group showed increased bladder volume and patchy congestion compared to the uninfected group, indicating significant inflammation. Figure 8F), while the bladder volume in the Cu-ZIF8-Ru@Gel group was smaller than that in the Cu-ZIF8 group and the Cu-ZIF8-Ru group, and the bladder volume and color in the Cu-ZIF8-Ru@Gel+Laser group were more similar to those in the uninfected group, indicating that the inflammation was reduced. In addition, the kidney tissue collected after treatment showed that the kidney tissue volume in the Control group was smaller and the color was lighter red than that in the uninfected group (F). Figure 8 G), consistent with the characteristics of ascending infection affecting kidney tissue. The kidney volume and color in the Cu-ZIF8-Ru@Gel group were closer to the uninfected group than in the Cu-ZIF8 and Cu-ZIF8-Ru groups, indicating that the inflammation caused by ascending infection was initially controlled. The kidney volume and color in the Cu-ZIF8-Ru@Gel+Laser group were closest to the uninfected group, suggesting the best therapeutic effect. Changes in mouse body weight also indirectly reflected the impact of inflammation on the kidneys ( Figure 8 The results showed that after treatment, the mice in the Control group had a lower body weight than the other groups, while the body weight changes in the Cu-ZIF8-Ru@Gel group and the Cu-ZIF8-Ru@Gel+Laser group were most similar to those in the uninfected group, indicating that inflammation in urinary tract infection was controlled, reducing ascending infection and thus protecting the kidneys.

[0115] To better evaluate the efficacy of Cu-ZIF8-Ru@Gel in treating recurrent urinary tract infections, blood samples from mice in each group were collected after treatment to detect C-reactive protein (CRP) levels and for routine blood tests. CRP is one of the most sensitive indicators of nonspecific inflammatory responses and can rapidly assess the severity of inflammation. Figure 8 As shown in Figure I, the significantly higher C-reactive protein (CRP) levels in the Control group compared to the uninfected group indicate the highest level of systemic inflammation. The CRP levels in the Cu-ZIF8-Ru@Gel group were lower than those in the Cu-ZIF8 and Cu-ZIF8-Ru groups, suggesting that Cu-ZIF8-Ru@Gel can effectively reduce systemic inflammation. Notably, the slight increase in CRP levels in the Cu-ZIF8-Ru@Gel+Laser group was closest to that in the uninfected group, suggesting that it can significantly inhibit systemic inflammation. Furthermore, comparisons of inflammatory cell counts (white blood cells, neutrophils, and lymphocytes) across groups (…) Figure 8 The control group showed a significantly higher increase in inflammatory cells compared to the uninfected group, indicating severe and persistent infection. After treatment, the Cu-ZIF8-Ru@Gel group showed a further decrease in inflammatory cells compared to the Cu-ZIF8 and Cu-ZIF8-Ru groups, while the Cu-ZIF8-Ru@Gel+Laser group showed cells most similar to the uninfected group. This indicates that Cu-ZIF8-Ru@Gel can effectively control the inflammatory response, and this effect is further enhanced after laser irradiation.

[0116] After treatment, half of the bladder and kidney were homogenized and smeared for quantification of bacterial count in the bladder and kidneys to assess treatment effectiveness. Figure 8 As shown in K, the dense colonies in the Control group indicated a high bladder infection load. The reduced colonies in the Cu-ZIF8-Ru group compared to the Cu-ZIF8 group indicated a better antibacterial effect, but it failed to control the bacterial infection in the bladder. The presence of only scattered colonies in the Cu-ZIF8-Ru@Gel group indicated a further enhanced bactericidal effect. The near absence of colonies in the Cu-ZIF8-Ru@Gel+Laser group after laser irradiation confirmed that Cu-ZIF8-Ru@Gel achieved the strongest bactericidal effect after laser irradiation. Quantitative results of bladder homogenate plating in each group further confirmed this conclusion. Figure 8 L). Furthermore, colony smears of kidney homogenates showed a large number of colonies in the Control group kidneys, suggesting ascending infection (L). Figure 8 M), while the colony counts of Cu-ZIF8-Ru@Gel and Cu-ZIF8-Ru@Gel+Laser groups were close to zero compared to the Cu-ZIF8 group and Cu-ZIF8-Ru group, indicating that they effectively control intrabladder bacterial infection and can block the ascending infection of MDR E. coli. Quantitative results of renal homogenate smears from each group further confirmed this conclusion. Figure 8 N).

[0117] Even after treatment, the Cu-ZIF8 group still showed a large number of diffuse infiltrations of neutrophils. Figure 9 A) The more regular urothelial structure and reduced neutrophil count in the Cu-ZIF8-Ru group indicate limited treatment efficacy. In contrast, the urothelial mucosa morphology in the Cu-ZIF8-Ru@Gel group was nearly normal, and the significantly reduced neutrophil infiltration indicated controlled inflammation. After laser irradiation, only a small number of neutrophil infiltrations were observed in the urothelial structure of the Cu-ZIF8-Ru@Gel+Laser group, and its urothelial mucosa morphology was most similar to the uninfected group. Furthermore, CD68 immunostaining results showed that the CD68 expression level was highest in the Control group (uninfected group), exhibiting diffuse infiltration, suggesting active chronic inflammation. The CD68 expression in the Cu-ZIF8-Ru group decreased slightly compared to the Cu-ZIF8 group, but only to a limited extent. The CD68 expression in the Cu-ZIF8-Ru@Gel group was significantly lower than in the Control group, demonstrating its significant inhibitory effect on inflammation. Importantly, after laser irradiation, the CD68 expression in the Cu-ZIF8-Ru@Gel+Laser group was close to that in the uninfected group, indicating that treatment effectively terminated inflammation.

[0118] IL-6, as an important pro-inflammatory cytokine in the inflammatory response, plays a crucial role in assessing the level of inflammation. IL-6 immunostaining results showed that the Control group exhibited strong positive diffuse expression of IL-6 compared to the uninfected group, consistent with the characteristics of chronic inflammation. The Cu-ZIF8 group also showed a large amount of strong positive diffuse distribution of IL-6 compared to the Control group. Although IL-6 expression in the Cu-ZIF8-Ru group decreased compared to the Cu-ZIF8 group, the therapeutic effect was limited. The significant decrease in IL-6 expression in the Cu-ZIF8-Ru@Gel group indicates its significant inhibition of the inflammatory cytokine storm. After laser irradiation, only a small amount of IL-6 expression was observed in the Cu-ZIF8-Ru@Gel+Laser group, indicating its optimal therapeutic effect on inflammation. Sustained TNF-α overexpression is one of the important factors driving inflammatory responses and tissue damage; its decrease is often consistent with inflammation remission. Immunostaining results for TNF-α showed extensive brownish-red positivity in the epithelium and lamina propria of the Control group compared to the uninfected group, indicating sustained and significant release of pro-inflammatory factors. Although TNF-α expression was decreased in the Cu-ZIF8-Ru group compared to the Cu-ZIF8 group, its inhibitory effect on inflammation was limited. Notably, the Cu-ZIF8-Ru@Gel group showed mostly weak positive staining, indicating a significant decrease in inflammatory burden, while after laser irradiation, the Cu-ZIF8-Ru@Gel+Laser group showed only sporadic or near-negative TNF-α signals, indicating significant inflammatory relief.

[0119] In summary, Cu-ZIF8-Ru@Gel significantly reduced mucosal edema and epithelial damage, inhibited macrophage infiltration, and downregulated pro-inflammatory factors, suggesting effective clearance of infection within the bladder.

[0120] H&E results of kidney tissue showed that the control group had moderate neutrophil infiltration and congestion compared with the uninfected group. Figure 9B) Mild degeneration of renal tubular epithelium; inflammatory changes were less pronounced in the Cu-ZIF8 and Cu-ZIF8-Ru groups compared to the Control group; the renal tubular structure in the Cu-ZIF8-Ru@Gel and Cu-ZIF8-Ru@Gel+Laser groups was closest to that of the uninfected group, showing more significant inhibition of inflammation and edema, with no signs of drug-related necrosis or hemorrhage. Furthermore, H&E results of renal tissue showed a diffuse increase in CD68-positive cells in the Control group, indicating an active macrophage response. The CD68-positive signal was slightly decreased in the Cu-ZIF8 and Cu-ZIF8-Ru groups, significantly decreased in the Cu-ZIF8-Ru@Gel group, and the CD68-positive signal in the Cu-ZIF8-Ru@Gel+Laser group was close to that of the uninfected group, indicating that Cu-ZIF8-Ru@Gel significantly inhibited ascending infection after laser irradiation. Similar results were observed in the expression of TNF-α signaling in each group. The control group showed mild positivity, indicating the release of pro-inflammatory factors. The Cu-ZIF8 and Cu-ZIF8-Ru groups showed a significant decrease in TNF-α positive signaling, while the Cu-ZIF8-Ru@Gel and Cu-ZIF8-Ru@Gel+Laser groups showed almost no TNF-α positive signaling, indicating that the ascending infection was under control. The Cu-ZIF8-Ru@Gel and Cu-ZIF8-Ru@Gel+Laser groups showed similar renal structure compared to the uninfected group, while the significant downregulation of CD68, IL-6, and TNF-α positive signals indicated that they effectively blocked ascending infection without significant nephrotoxicity.

[0121] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0122] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A copper-based nanozyme, characterized in that, The copper-based nanozyme comprises a copper-doped zeolite imidazole salt framework-8 metal-organic framework and a ruthenium complex; The preparation method of the copper-based nanozyme includes the following steps: Preparation of copper metal-organic frameworks: Under nitrogen protection, copper nitrate, zinc nitrate and 2-methylimidazole were dissolved in methanol, mixed and stirred, centrifuged and washed with methanol to obtain copper metal-organic frameworks; Preparation of copper-based nanozymes: phenanthroline, ruthenium trichloride trihydrate, lithium chloride, and dimethylformamide were mixed and stirred overnight. The mixture was then subjected to reduced pressure, acetone was added, and the mixture was filtered and washed to obtain cis-dichlorobis(1,10-phenanthroline)ruthenium(II). Phenazine ligands and cis-dichlorobis(1,10-phenanthroline)ruthenium(II) were dissolved in a mixed solvent of ethanol and water, refluxed under nitrogen, purified, subjected to anion exchange to remove volatiles, and recrystallized to obtain the ruthenium complex. Under a nitrogen-protected thermal environment, the ruthenium complex and a copper metal-organic framework were mixed, stirred in the dark, centrifuged, and washed with methanol to obtain copper-based nanozymes. According to the mass ratio, the phenanthroline : ruthenium trichloride trihydrate : lithium chloride is 1 : (0.1~1) : (0.5~2). The phenazine ligand is dppz.

2. The copper-based nanozyme according to claim 1, characterized in that, The mass ratio of the phenazine ligand to the cis-dichlorobis(1,10-phenanthroline)ruthenium(II) is 1:(0.1~1), the anion exchange is performed using potassium hexafluorophosphate, and the purification is performed using a silica gel column.

3. A temperature-sensitive hydrogel, characterized in that, The thermosensitive hydrogel includes the copper-based nanozyme according to any one of claims 1-2.

4. The method for preparing the thermosensitive hydrogel as described in claim 3, characterized in that, Includes the following steps: Under nitrogen protection, the initiator was degassed and stirred, D,L-lactide and glycolide were added and mixed, and a catalyst was added to react. After the reaction was completed, the mixture was poured into water at 3~5℃, stirred overnight, heated in a water bath, copper-based nanozyme was added and mixed, and then freeze-dried to obtain the thermosensitive hydrogel.

5. The preparation method according to claim 4, characterized in that, The initiator is polyethylene glycol, and the catalyst is stannous isooctanoate; According to the mass ratio, the total mass of D,L-lactide and glycolide is (1~3):1 of polyethylene glycol. According to the molar ratio, the D,L-lactide : the glycolide is (6~8):

1.

6. The use of the copper-based nanozyme as described in any one of claims 1-2 in the preparation of products for treating multidrug-resistant urinary tract infections.

Citation Information

Patent Citations

  • Thermosensitive hepatitis B vaccine

    CN102370978A